High strength steel sheet, manufacturing method therefor,

By controlling the composition and microstructure of high-strength steel plates, and combining heat treatment and plating treatment, the problem of shear end face damage of high-strength steel plates in corrosive environments has been solved, achieving a high yield ratio and good bending properties, and meeting the tensile strength requirements of over 1180MPa.

CN120981591APending Publication Date: 2025-11-18JFE STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380096206.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-05
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing high-strength steel plates suffer severe shear damage in corrosive environments, making it difficult to simultaneously meet the requirements of a high yield ratio (YR) and flexural properties, while achieving a tensile strength of over 1180 MPa.

Method used

By controlling the composition and microstructure of the steel plate, a martensite-based microstructure is formed, the volume fraction of retained austenite is limited, the Si concentration deviation is reduced, and a soft layer is formed on the surface. Combined with appropriate heat treatment processes and plating treatments, the corrosion resistance and bending properties of the steel plate are improved.

Benefits of technology

It achieves a tensile strength of over 1180 MPa, a yield ratio (YR) of over 65%, and exhibits reduced damage to the shear end face under corrosive conditions, as well as good bending performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005607018200000311
    Figure BDA0005607018200000311
  • Figure BDA0005607018200000321
    Figure BDA0005607018200000321
  • Figure BDA0005607018200000331
    Figure BDA0005607018200000331
Patent Text Reader

Abstract

Provided is a high-strength steel sheet which has a high YR and high bendability, and which has a reduced degree of damage to a sheared end surface in a corrosive environment, and which has a TS of at least 1180 MPa. A high-strength steel sheet having: a component composition containing, in mass%, 0.030% to 0.500% of C, 0.01% to 2.50% of Si, 0.10% to 5.00% of Mn, 0.100% or less of P, 0.0200% or less of S, 1.000% or less of Al, 0.0100% or less of N, and 0.0100% or less of O, with the remainder being Fe and unavoidable impurities; in the steel structure, the area ratio of martensite is 40% or more, the area ratio of ferrite is 70% or less, and the volume ratio of retained austenite is 20.0% or less at the position of 1 / 4 of the sheet thickness. The ratio of the standard deviation of the Si concentration to the average value of the Si concentration is 1.00 or less at the position 1 / 2 of the sheet thickness.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a high-strength steel sheet and a manufacturing method thereof, a member, and an automobile member. BACKGROUND

[0002] In order to improve the crashworthiness while achieving reduction in CO2 emissions by lightening of vehicles, high-strength of steel sheets for automobiles is being promoted. In addition, in the background of the successive introduction of new laws and regulations, examples of application of high-strength steel sheets to main structural members, reinforcing members (hereinafter, also referred to as "skeletal structural members of automobiles" and the like) that form the skeleton of the passenger compartment of automobiles for the purpose of increasing the strength of the vehicle body are gradually increasing, and in particular, examples of application of high-strength steel sheets having a tensile strength (hereinafter, also referred to as "TS") of 1180 MPa or more are significantly increasing.

[0003] In forming into a desired shape, the high-strength steel sheet used for the skeletal structural members of automobiles and the like is required to have a high member strength. For the improvement of the member strength, for example, increasing the yield ratio (YR = YS / TS x 100. Hereinafter, also referred to as "YR") of the steel sheet is effective. Thereby, the impact absorbing energy at the time of automobile collision is improved.

[0004] Further, for example, a crash box and the like in the skeletal structural members of automobiles and the like have a bending processed portion. Therefore, from the viewpoint of formability, it is preferable to apply a steel sheet having high bendability in such members.

[0005] As a technology relating to such a high-strength steel sheet, for example, in claim 1 of Patent Literature 1, "An alloyed hot-dip galvanized steel sheet having an alloyed hot-dip galvanized layer on the surface of the steel sheet, characterized in that the steel sheet has the following composition consisting of, in mass%, C: 0.03 to 0.35%, Si: 0.005 to 2.0%, Mn: 1.0 to 4.0%, P: 0.0004 to 0.1%, S: 0.02% or less, sol. Al: 0.0002 to 2.0%, and N: 0.01% or less, with the remainder consisting of Fe and impurities, an average interval in the rolling straight angle direction of the enriched portion of Mn and / or Si enriched toward the rolling direction at a position at a depth of 50 μm from the surface of the steel sheet, i.e., an average interval of the enriched portion is 1000 μm or less, a number density of cracks at a depth of 3 to 10 μm from the surface of the steel sheet is 3 to 1000 pieces / mm, and has the following steel structure consisting of, in area%, 60% or more of bainite, 1% or more of retained austenite, 1% or more of martensite, and 2% or more and less than 20% of ferrite, and an average value of the closest distance of the martensite and the retained austenite, i.e., an average interval of the super-hard phase is 20 μm or less, the alloyed hot-dip galvanized steel sheet has mechanical properties with a tensile strength (TS) of 780 MPa or more" is disclosed.

[0006] Prior Art Documents

[0007] Patent Documents

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2012-219342 SUMMARY

[0009] Among the members used for the portions exposed to a corrosive environment in a skeletal structural member of an automobile, there is a member which can be damaged due to shear end face corrosion in the use environment of the automobile. From this point of view, it is desirable that the degree of damage of the shear end face in a corrosive environment be reduced for a high-strength steel sheet.

[0010] However, in the high-strength steel sheet described in Patent Document 1, the degree of damage of the shear end face in a corrosive environment is not considered. Therefore, the current situation is that, from the viewpoint of increasing the application rate of a high-strength steel sheet having TS of 1180 MPa or more in skeletal structural members of an automobile and the like, there is a need to develop a high-strength steel sheet having TS of 1180 MPa or more, which has high YR and high bendability, and in which the degree of damage of the shear end face in a corrosive environment is reduced.

[0011] The present application was accomplished in view of the above-described current situation, and aims to provide a high-strength steel sheet having high YR and high bendability, and in which the degree of damage of the shear end face in a corrosive environment is reduced, and TS is 1180 MPa or more.

[0012] In addition, the present application also aims to provide a method for manufacturing the above-described high-strength steel sheet.

[0013] Furthermore, the present application also aims to provide a member made using the above-described high-strength steel sheet.

[0014] Here, "high YR" means that YR is 65% or more. YR is calculated by the following formula (2).

[0015] YR = YS / TS x 100 (2) TS and YS are each measured in accordance with JIS Z 2241.

[0016] Here, "high bendability" means that, in a bend test performed in accordance with JIS Z 2248 (see the description of the examples described later for details), when evaluation is performed on whether or not a crack is generated at the ridge portion at the apex of the bend, no crack is generated or a micro crack of less than 200 μm is generated.

[0017] Here, "reduction in the degree of damage of the shear end face in a corrosive environment" means that, in the hydrochloric acid immersion test described in the examples described later, the crack length of the shear end face of the test piece after hydrochloric acid immersion is 300 μm or less.

[0018] The present inventors have conducted intensive studies in order to achieve the above object, and as a result, have arrived at the following insights.

[0019] (1) By forming a structure in which martensite (quenched martensite and tempered martensite) is the main component, a high YR can be achieved.

[0020] (2) By making the volume fraction of residual austenite 20% or less, a high bendability and a reduction in the degree of damage to the sheared end surface in a corrosive environment can be achieved.

[0021] (3) By making the value of the ratio of the standard deviation of the Si concentration at the 1 / 2-thickness position to the average value of the Si concentration (hereinafter also referred to as "standard deviation of Si concentration / average Si concentration") 1.00 or less, a reduction in the degree of damage to the sheared end surface in a corrosive environment can be achieved.

[0022] The present application was completed in accordance with the above insights. That is, the gist of the present application is as follows.

[0023] [1] A high-strength steel sheet having the following composition and steel structure,

[0024] the composition containing, in mass%, C: 0.030% to 0.500%, Si: 0.01% to 2.50%, Mn: 0.10% to 5.00%, P: 0.100% or less, S: 0.0200% or less, Al: 1.000% or less, N: 0.0100% or less, and O: 0.0100% or less, with the remainder consisting of Fe and unavoidable impurities;

[0025] in the steel structure, at the 1 / 4-thickness position, the area fraction of martensite is 40% or more, the area fraction of ferrite is 70% or less, and the volume fraction of residual austenite is 20.0% or less;

[0026] at the 1 / 2-thickness position, the ratio of the standard deviation of the Si concentration to the average value of the Si concentration is 1.00 or less.

[0027] [2] The high-strength steel sheet according to [1], wherein the composition further contains, in mass%, at least one element selected from the group consisting of Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 0.010% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

[0028] [3] The high-strength steel sheet according to [1] or [2], wherein the high-strength steel sheet has a surface soft layer which is a region having a Vickers hardness of 85% or less at a position of 1 / 4 of a thickness direction depth from a surface of the high-strength steel sheet, and is a region within 200 μm from the surface of the high-strength steel sheet in the thickness direction,

[0029] when the nano hardness of 300 or more points is measured in a region of 50 μm x 50 μm of each surface at a position of 1 / 4 of the thickness direction depth and a position of 1 / 2 of the thickness direction depth from the surface of the high-strength steel sheet to the surface soft layer,

[0030] a proportion of the number of measurement points of the nano hardness of the surface at a position of 1 / 4 of the thickness direction depth from the surface of the high-strength steel sheet to the surface soft layer being 7.0 GPa or more is 0.10 or less with respect to the total number of measurement points,

[0031] furthermore, a standard deviation σ of the nano hardness of the surface at a position of 1 / 4 of the thickness direction depth from the surface of the high-strength steel sheet to the surface soft layer is 1.8 GPa or less,

[0032] furthermore, a standard deviation σ of the nano hardness of the surface at a position of 1 / 2 of the thickness direction depth from the surface of the high-strength steel sheet to the surface soft layer is 2.2 GPa or less.

[0033] [4] The high-strength steel sheet according to any one of [1] to [3], wherein a metal plating layer is provided on a surface of one side or both sides of the high-strength steel sheet, and the metal plating layer contains one or two or more kinds selected from the group consisting of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi in a total of 50 mass% or more.

[0034] [5] The high-strength steel sheet according to any one of [1] to [4], wherein a plated layer containing at least one of zinc and aluminum in a total of 50 mass% or more is provided on the outermost layer of one side or both sides of the high-strength steel sheet.

[0035] [6] A method for manufacturing a high-strength steel sheet, comprising the steps of:

[0036] casting molten steel having the composition of [1] or [2], and then cooling the molten steel at an average cooling rate of 3.0°C / hr or more in a temperature range of 500°C to 700°C, and at an average cooling rate of 1.0°C / hr or more in a temperature range of 400°C or more and less than 500°C, to obtain a steel billet;

[0037] heating the steel billet to a slab heating temperature Tl of 1150°C or more, and then performing hot rolling at a coiling temperature of 600°C or less and a residence time in a temperature range of 300°C to 400°C during cooling after coiling of 50,000 seconds or less to obtain a hot-rolled sheet, wherein, in the heating of the steel billet, a residence time in a temperature range of 1100°C to Tl is 20 minutes or more;

[0038] performing pickling on the hot-rolled sheet;

[0039] performing cold rolling on the hot-rolled sheet subjected to the pickling to obtain a cold-rolled sheet;

[0040] defining a temperature defined by [1] as an Ac3 point (°C), and performing heating of the cold-rolled sheet to a heating temperature T2 of the Ac3 point or more at an average heating rate of 10°C / s or more in a temperature range of 250°C to 700°C, thereby annealing the cold-rolled sheet, wherein a residence time in a temperature range of 750°C or more and less than the Ac3 point is 200 seconds or less; and

[0041] cooling the cold-rolled sheet subjected to the annealing at an average cooling rate of 1.0°C / s or more in a temperature range of 250°C to 400°C to obtain a high-strength steel sheet.

[0042] Ac3 point (°C) = 910 - 203 x [%C] + 44.7 x [%Si] - 30 x [%Mn] + 700 x [%P] + 400 x [%Al] + 400 x [%Ti] + 104 x [%V] + 13.1 x [%W] - 11 x [%Cr] + 31.5 x [%Mo] - 15.2 x [%Ni] - 20 x [%Cu] 1 / 2

[0043] [1]

[0044] ​In the formula, [%X] represents the content of the component element X in the steel (mass %), and is set to 0 when not contained.

[0045] [7] The method for manufacturing a high-strength steel sheet according to [6], wherein, in the annealing step of the cold-rolled sheet, the oxygen concentration of the atmosphere in the temperature range of 250°C to 700°C is 2 to 30 volume ppm, and the dew point of the atmosphere at the heating temperature T2 is -35°C or higher.

[0046] [8] The method for manufacturing a high-strength steel sheet according to [6] or [7], wherein, in the cooling step of the cold-rolled sheet after the annealing, a soaking step at a temperature T3 of 100°C or higher to 450°C or lower for 5 seconds or longer is provided.

[0047] [9] The method for manufacturing a high-strength steel sheet according to any one of [6] to [8], wherein, in the cooling step of the cold-rolled sheet after the annealing, the cooling is stopped at a cooling stop temperature T4 of 250°C or lower, and then reheating to a temperature of (T4 + 50°C) or higher to 450°C or lower is performed, and soaking at the temperature for 5 seconds or longer is performed.

[0048]

[10] The method for manufacturing a high-strength steel sheet according to any one of [6] to [9], comprising a step of, before the annealing of the cold-rolled sheet, plating one or both sides of the cold-rolled sheet with a metal selected from one or two or more of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi, in a total amount of 50 mass % or more.

[0049]

[11] The method for manufacturing a high-strength steel sheet according to any one of [6] to

[10] , comprising a step of, after the cooling of the cold-rolled sheet after the annealing, performing a plating treatment to plate the metal selected from at least one of zinc and aluminum in a total amount of 50 mass % or more.

[0050]

[12] A member comprising at least a part of the high-strength steel sheet according to any one of [1] to [5].

[0051]

[13] An automobile member comprising the member according to

[12] .

[0052] According to the present application, it is possible to provide a high-strength steel sheet having a TS of 1180 MPa or more, high YR, and high bendability, and reduced damage to the sheared end surface in a corrosive environment, and a method for manufacturing the same. BRIEF DESCRIPTION OF DRAWINGS

[0053] Figure 1 is a schematic view of the production of a sample for a U bend + tight bend test according to the example.Figure 1 (a) about U-bending processing (primary bending processing), Figure 1 (b) about bending (secondary bending processing).

[0054] Figure 2 is a schematic view about the production of a sample for a V-bending + orthogonal VDA bending test of the example. Figure 2 (a) about V-bending processing (primary bending processing), Figure 2 (b) about orthogonal VDA bending (secondary bending processing).

[0055] Figure 3 is a schematic view about a sample and a test for an axial crush test of the example. Figure 3 (a) is a front view of a test member, Figure 3 (b) is a front view of a test member. Figure 3 (c) is a schematic view showing an axial crush test. DETAILED DESCRIPTION

[0056] The present application is explained based on the following examples. The present application is not limited to the following examples.

[0057] [1] High-strength steel sheet

[0058] [1-1] Component composition

[0059] First, the component composition of the high-strength steel sheet of the present application is explained. It should be noted that in the following explanation, the content of the component elements of steel expressed as "%" means "mass %" unless otherwise specified.

[0060] [C: 0.030% to 0.500%]

[0061] C is one of the important basic components of steel, and in particular in the present application, is an important element that affects the area ratio of martensite, ferrite, and residual austenite. When the content of C is less than 0.030%, the area ratio of martensite decreases, and it is difficult to achieve the desired TS. On the other hand, if the content of C exceeds 0.500%, the martensite embrittles, and in addition, the residual austenite increases, and the amount of martensite that phase changes from the residual austenite increases, so the bendability decreases. In addition, due to the increase in residual austenite, cracks are formed at the shear end face at the time of shearing, so the crack length after hydrochloric acid immersion increases, and the degree of damage to the shear end face in a corrosive environment deteriorates. Therefore, the content of C is set to 0.030% to 0.500%. The content of C is preferably 0.050% or more, more preferably 0.070% or more, and in addition, is preferably 0.400% or less, more preferably 0.300% or less.

[0062] [Si: 0.01% to 2.50%]

[0063] Si is one of important essential components of the steel, and in particular, in the present application, it is an element that suppresses carbide generation in continuous annealing and promotes residual austenite generation, and thus affects the hardness of the martensite and the area ratio of the residual austenite. When the content of Si is less than 0.01%, the martensite is tempered, and it is difficult to achieve the desired TS. On the other hand, if the content of Si exceeds 2.50%, segregation of Si becomes significant, the standard deviation of the Si concentration at the 1 / 2 position of the sheet thickness / average Si concentration increases, and the degree of damage to the shear end surface in a corrosive environment deteriorates. In addition, the residual austenite increases, the amount of the martensite transformed from the residual austenite increases, and thus the bendability decreases. Therefore, the content of Si is set to 0.01% to 2.50%. The content of Si is preferably 0.05% or more, more preferably 0.10% or more, and in addition, it is preferably 2.00% or less, more preferably 1.80% or less.

[0064] [Mn: 0.10% to 5.00%]

[0065] Mn is one of important essential components of the steel, and in particular, in the present application, it is an important element that affects the area ratio of the martensite. When the content of Mn is less than 0.10%, the area ratio of the martensite decreases, and it is difficult to achieve a TS of 1180 MPa or more. On the other hand, if the content of Mn exceeds 5.00%, segregation of Mn becomes significant, as a result of which segregation of Si also becomes significant, and thus the standard deviation of the Si concentration at the 1 / 2 position of the sheet thickness / average Si concentration increases, and the degree of damage to the shear end surface in a corrosive environment deteriorates. In addition, the residual austenite increases, the amount of the martensite transformed from the residual austenite increases, and thus the bendability decreases. Therefore, the content of Mn is set to 0.10% to 5.00%. The content of Mn is preferably 0.80% or more, more preferably 1.00% or more, and in addition, it is preferably 4.50% or less, more preferably 4.00% or less.

[0066] [P: 0.100% or less]

[0067] P is an element that causes the grain boundary at the prior austenite grain boundary to be embrittled, and decreases the limit deformation capacity of the steel sheet, and the bendability can also decrease. Therefore, the content of P is set to 0.100% or less, and it is preferably 0.070% or less. The lower limit of the content of P is not particularly limited, P is a solid solution strengthening element, and thus it is preferably 0.001% or more, because it can increase the strength of the steel sheet.

[0068] [S: 0.0200% or less]

[0069] S is an element that exists as a sulfide and reduces the limit deformation capacity of the steel sheet, and the bendability is reduced. Therefore, the content of S is set to 0.0200% or less, and preferably 0.0050% or less. The lower limit of the content of S is not particularly limited, and due to a limitation in production technology, the content of S is preferably 0.0001% or more.

[0070] [Al: 1.000% or less]

[0071] Al is an element that raises the A3 transformation point, and the ferrite in the steel structure increases, and it is difficult to achieve the desired YR. Therefore, the content of Al is set to 1.000% or less, and preferably 0.500% or less. The lower limit of the content of Al is not particularly limited, but in order to suppress the generation of carbides in continuous annealing and promote the generation of residual austenite, the content of Al is preferably 0.001% or more.

[0072] [N: 0.0100% or less]

[0073] N is an element that exists as a nitride and reduces the limit deformation capacity of the steel sheet, and the bendability can be reduced. Therefore, the content of N is set to 0.0100% or less, and preferably 0.0050% or less. The lower limit of the content of N is not particularly limited, and due to a limitation in production technology, the content of N is preferably 0.0001% or more.

[0074] [O: 0.0100% or less]

[0075] O is an element that exists as an oxide and reduces the limit deformation capacity of the steel sheet, and the bendability can be reduced. Therefore, the content of O is set to 0.0100% or less, and preferably 0.0050% or less. The lower limit of the content of O is not particularly limited, and due to a limitation in production technology, the content of O is preferably 0.0001% or more.

[0076] [Arbitrary components]

[0077] In the high-strength steel sheet of the present application, in addition to the above-mentioned component composition, at least one element selected from the group consisting of Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 0.010% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.020% or less, Te: 0.020% or less, Hf: 0.10% or less, and Bi: 0.200% or less can be further contained in mass%. These elements can be added alone or in combination of two or more.

[0078] When Ti, Nb or V is contained, in order to avoid generation of a large amount of coarse precipitates, inclusions, decrease in limit ductility of the steel sheet, decrease in bendability, the content of Ti, Nb or V is respectively preferably 0.200% or less, more preferably 0.100% or less. The lower limit of the content of Ti, Nb or V is not particularly limited, but at the time of hot rolling or at the time of continuous annealing, fine carbides, nitrides or carbonitrides are formed, and the strength of the steel sheet is increased, and therefore the content of Ti, Nb or V is respectively preferably 0.001% or more.

[0079] When Ta or W is contained, in order to avoid generation of a large amount of coarse precipitates, inclusions, decrease in limit ductility of the steel sheet, decrease in bendability, the content of Ta or W is respectively preferably 0.10% or less, more preferably 0.08% or less. The lower limit of the content of Ta or W is not particularly limited, but at the time of hot rolling or at the time of continuous annealing, fine carbides, nitrides or carbonitrides are formed, and the strength of the steel sheet is increased, and therefore the content of Ta or W is respectively preferably 0.01% or more.

[0080] When B is contained, in order to avoid generation of cracks in the steel sheet at the time of casting or at the time of hot rolling, decrease in limit ductility of the steel sheet, and further decrease in bendability, the content of B is preferably 0.0100% or less, more preferably 0.0080% or less. The lower limit of the content of B is not particularly limited, but since B is an element which increases hardenability by segregating at the grain boundaries of austenite in annealing, the content of B is preferably 0.0003% or more.

[0081] When Cr, Mo or Ni is contained, in order to avoid increase in coarse precipitates, inclusions, decrease in limit ductility of the steel sheet, and further decrease in bendability, the content of Cr, Mo or Ni is respectively preferably 1.00% or less, more preferably 0.80% or less. The lower limit of the content of Cr, Mo or Ni is not particularly limited, but since Cr, Mo or Ni is an element which increases hardenability, the content of Cr, Mo or Ni is respectively preferably 0.01% or more.

[0082] When Co is contained, in order to avoid increase in coarse precipitates, inclusions, decrease in limit ductility of the steel sheet, and further decrease in bendability, the content of Co is preferably 0.010% or less, more preferably 0.008% or less. The lower limit of the content of Co is not particularly limited, but since Co is an element which increases hardenability, the content of Co is preferably 0.001% or more.

[0083] When Cu is contained, in order to avoid an increase in coarse precipitates and inclusions, a decrease in the limit of deformability of the steel sheet, and a further decrease in bendability, the content of Cu is preferably 1.00% or less, more preferably 0.80% or less. The lower limit of the content of Cu is not particularly limited, but since Cu is an element that improves hardenability, the content of Cu is preferably 0.01% or more.

[0084] When Sn is contained, in order to avoid the generation of cracks in the steel sheet during casting or hot rolling, a decrease in the limit of deformability of the steel sheet, and a further decrease in bendability, the content of Sn is preferably 0.200% or less, more preferably 0.100% or less. It should be noted that the lower limit of the content of Sn is not particularly limited, but since Sn is an element that improves hardenability, the content of Sn is preferably 0.001% or more.

[0085] When Sb is contained, in order to avoid an increase in coarse precipitates and inclusions, a decrease in the limit of deformability of the steel sheet, and a further decrease in bendability, the content of Sb is preferably 0.200% or less, more preferably 0.100% or less. The lower limit of the content of Sb is not particularly limited, but since Sb is an element that controls the thickness of softening of the surface layer and adjusts the strength, the content of Sb is preferably 0.001% or more.

[0086] When Ca, Mg, or REM is contained, in order to avoid an increase in coarse precipitates and inclusions, a decrease in the limit of deformability of the steel sheet, and a further decrease in bendability, the content of Ca, Mg, or REM is preferably 0.0100% or less, more preferably 0.0050% or less, respectively. The lower limit of the content of Ca, Mg, or REM is not particularly limited, but since Ca, Mg, or REM is an element that spheroidizes the shape of nitrides and sulfides and improves the limit of deformability of the steel sheet, the content of Ca, Mg, or REM is preferably 0.0005% or more, respectively.

[0087] When Zr or Te is contained, in order to avoid an increase in coarse precipitates and inclusions, a decrease in the limit of deformability of the steel sheet, and a further decrease in bendability, the content of Zr or Te is preferably 0.100% or less, more preferably 0.080% or less, respectively. It should be noted that the lower limit of the content of Zr or Te is not particularly limited, but since Zr or Te is an element that spheroidizes the shape of nitrides and sulfides and improves the limit of deformability of the steel sheet, the content of Zr or Te is preferably 0.001% or more, respectively.

[0088] When Hf is contained, in order to avoid an increase in coarse precipitates and inclusions, a decrease in the limit of deformability of the steel sheet, and a further decrease in bendability, the content of Hf is preferably 0.10% or less, more preferably 0.08% or less. The lower limit of the content of Hf is not particularly limited, but since Hf is an element that spheroidizes the shape of nitrides and sulfides and improves the limit of deformability of the steel sheet, the content of Hf is preferably 0.01% or more.

[0089] When Bi is contained, in order to avoid the increase of coarse precipitates, inclusions, the limit ductility of the steel sheet decreases, and further the bendability decreases, the content of Bi is preferably 0.200% or less, more preferably 0.100% or less. The lower limit of the content of Bi is not particularly limited, but since Bi is an element that reduces segregation, the content of Bi is preferably 0.001% or more.

[0090] The high-strength steel sheet of the present application has the following composition consisting of essential components and optional components as the case requires, with the remainder consisting of Fe and unavoidable impurities. Here, as the unavoidable impurities, Zn, Pb, As, Ge, Sr, and Cs can be given. These unavoidable impurities are allowed to be contained in a total amount of 0.100% or less.

[0091] [1-2] Steel structure

[0092] The steel structure of the high-strength steel sheet of the present application is described.

[0093] [Area ratio of martensite: 40% or more]

[0094] When the area ratio of martensite is less than 40%, it is difficult to achieve TS of 1180 MPa or more, high YR, and high bendability. Therefore, the area ratio of martensite is set to 40% or more. The area ratio of martensite is preferably 55% or more, more preferably 60% or more, and further preferably 80% or more. The upper limit of the area ratio of martensite is not particularly limited, and even if it is 100%, the desired characteristics can be obtained.

[0095] Here, the martensite referred to herein includes not only quenched martensite (fresh martensite) but also tempered martensite and bainite. The observation position of the area ratio of martensite is set to the 1 / 4 position of the sheet thickness of the steel sheet as described later.

[0096] [Area ratio of ferrite: 70% or less]

[0097] If the area ratio of ferrite exceeds 70%, it is difficult to achieve TS of 1180 MPa or more, high YR, and high bendability. Therefore, the area ratio of ferrite is set to 70% or less. The area ratio of ferrite is preferably 50% or less, more preferably 40% or less, and further preferably 30% or less. The lower limit of the area ratio of ferrite is not particularly limited, and even if it is 0%, the desired characteristics can be obtained. Here, the ferrite referred to herein includes bainite ferrite. It should be noted that the observation position of the area ratio of ferrite is set to the 1 / 4 position of the sheet thickness of the steel sheet as described later.

[0098] Here, the measurement method of the area ratio of martensite (quenched martensite, tempered martensite, and bainite) and ferrite (bainite ferrite) is as follows.

[0099] A sample was cut out from the steel sheet in a manner that a plate thickness section (L section) parallel to the rolling direction of the steel sheet was used as an observation surface. The observation surface of the sample was mirror-polished using a diamond polishing paste, and then, fine-polished using alumina, and further etched with 3% nitric acid ethanol to reveal the structure.

[0100] Next, for the sample, the plate thickness 1 / 4 position of the latter half was used as an observation surface, and observation was performed at a magnification of 3000 times using a scanning electron microscope (SEM) under conditions of an acceleration voltage of 10 kV, and SEM images of 3 fields of view (40 μm x 30 μm each) were obtained.

[0101] From the obtained SEM images, the area ratio of each structure (ferrite (bainitic ferrite), martensite (quenched martensite, tempered martensite, and bainite)) was calculated using Adobe Photoshop (manufactured by Adobe Systems Inc.). Specifically, the value obtained by dividing the area of each structure by the measurement area was used as the area ratio of each structure. The area ratio of each structure was calculated for 3 fields of view, and the average value thereof was used as the area ratio of each structure.

[0102] In the SEM images, the ferrite (bainitic ferrite) is a flat structure that is a concave structure and does not contain carbides, the tempered martensite and the bainite are concave structures and contain fine carbides, and the quenched martensite is a convex structure and has fine concavities and convexities inside the structure, and can be distinguished from each other. Note that since the tempered martensite and the bainite are the total area ratio as the area ratio of the martensite, they can not be distinguished from each other.

[0103] Note that since the steel structure of the steel sheet is generally substantially symmetrical in the plate thickness direction, in the identification of the structure and the measurement of the volume fraction of the retained austenite and the thickness of the surface soft layer described later, either one of the surfaces (front surface and back surface) of the steel sheet can be used as a representative, for example, either one of the surfaces (front surface and back surface) of the steel sheet can be used as the starting point (0 position in the plate thickness) of the plate thickness position such as the plate thickness 1 / 4 position. The same applies hereinafter.

[0104] [Volume fraction of retained austenite: 20.0% or less]

[0105] In the case where the volume fraction of residual austenite exceeds 20.0%, the bendability decreases due to an increase in the amount of martensite transformed from the residual austenite. In addition, the crack length after immersion in hydrochloric acid increases due to the formation of cracks at the sheared end surface at the time of shearing, and the degree of damage to the sheared end surface in a corrosive environment deteriorates. Therefore, the volume fraction of residual austenite is set to 20.0% or less. The volume fraction of residual austenite is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less. The lower limit of the volume fraction of residual austenite is not particularly limited, and even if it is 0%, the desired properties can be obtained.

[0106] The observation position of the volume fraction of residual austenite is set to the 1 / 4 position of the thickness of the steel sheet, and the measurement method is as follows.

[0107] First, the steel sheet is ground so that the 1 / 4 position of the thickness of the steel sheet (the position corresponding to 1 / 4 of the thickness in the depth direction from the surface of the steel sheet) serves as the measurement surface, and then further ground by 0.1 mm by chemical polishing to obtain a sample.

[0108] The integrated reflection intensity of the (200) plane, the (220) plane, and the (311) plane of fcc iron (austenite), and the (200) plane, the (211) plane, and the (220) plane of bcc iron is measured for the measurement surface of the sample by an X-ray diffractometer using a Co Kα ray source.

[0109] The intensity ratio of the integrated reflection intensity of each plane from fcc iron to the integrated reflection intensity of each plane from bcc iron is calculated. The average of the 9 intensity ratios is taken as the volume fraction of residual austenite.

[0110] [Remaining portion structure]

[0111] The steel structure of the present application can also have a structure other than the above-described martensite, ferrite, and residual austenite (remaining portion structure).

[0112] As the remaining portion structure, a structure other than the above-described martensite, ferrite, and residual austenite can be cited, and as a known structure of the structure of the steel sheet, for example, includes pearlite, cementite, metastable carbide (epsilon (ε) carbide, eta (η) carbide, chi (χ) carbide, etc.), and the like. The identification of the remaining portion structure can be performed by, for example, SEM observation.

[0113] The area fraction of the remaining portion structure at the 1 / 4 position of the thickness of the steel sheet is preferably 5% or less, and can also be 0%.

[0114] The area fraction of the remaining portion structure is calculated by the following formula.

[0115] [Area rate of remaining structure (%)] = 100 - [Area rate of martensite (%)] - [Area rate of ferrite (%)] - [Volume rate of retained austenite (%)]

[0116] [1-3] Standard deviation of Si concentration at the 1 / 2-thickness position / average Si concentration

[0117] The value of the ratio of the standard deviation of Si concentration to the average value of Si concentration (standard deviation of Si concentration / average Si concentration) is a very important feature in the present application, and by reducing the standard deviation of Si concentration / average Si concentration, in other words, by suppressing segregation of Si, the degree of damage to the sheared end surface in a corrosive environment can be reduced. In order to obtain such an effect, the standard deviation of Si concentration at the 1 / 2-thickness position / average Si concentration is set to 1.00 or less, preferably 0.80% or less, more preferably 0.60% or less, and further preferably 0.50% or less. The lower limit of the standard deviation of Si concentration at the 1 / 2-thickness position / average Si concentration is not particularly limited, and even if it is 0, the desired properties can be obtained.

[0118] Here, the method of measuring the standard deviation of Si concentration at the 1 / 2-thickness position / average Si concentration is as follows.

[0119] A sample is cut out from the steel sheet in a manner such that a cross section in the thickness direction parallel to the rolling direction (L cross section) is the observation surface. The observation surface of the sample is polished. Next, mirror polishing is performed on the observation surface of the sample using a diamond polishing paste, and then, fine polishing is performed using alumina.

[0120] Next, on the observation surface of the sample, the Si concentration is measured using an electron beam microanalyzer (EPMA; Electron Probe Micro Analyzer) with the center position of the thickness of the steel sheet as the observation position (i.e., the center position of the thickness of the steel sheet (1 / 2-thickness position) is taken as the center position in the thickness direction of the measurement area), under the conditions of an acceleration voltage of 15 kV, a measurement area of 500 μm x 800 μm, a beam diameter of 2.0 μm, and a number of measurement points of 250 x 400 (lattice shape with a measurement interval of 2 μm), and the standard deviation of Si concentration at the 1 / 2-thickness position / average Si concentration is calculated. The average value of the values calculated in three regions is taken as the standard deviation of Si concentration at the 1 / 2-thickness position / average Si concentration.

[0121] [1-4] Thickness of the steel sheet

[0122] The thickness of the high-strength steel sheet of the present application is not particularly limited, and is typically 0.3 mm to 2.8 mm.

[0123] [1-5] Surface soft layer

[0124] The surface layer of the high-strength steel sheet according to the present application is preferably a soft layer (surface layer soft layer). The surface layer soft layer is effective in suppressing the progress of a bending crack at the time of press forming and at the time of a vehicle body collision, and thus enables further improvement in bendability.

[0125] The surface layer refers to a region corresponding to a thickness of 200 μm from the surface of the high-strength steel sheet in the thickness direction.

[0126] When the high-strength steel sheet is a hot-dip galvanized steel sheet, an alloyed hot-dip galvanized steel sheet, an electrogalvanized steel sheet, or another plated steel sheet subjected to plating treatment, the surface layer of the high-strength steel sheet refers to a region corresponding to a thickness of 200 μm from the surface of the steel sheet serving as a base material (substrate) of various plating layers in the thickness direction.

[0127] The soft layer refers to a region in which the Vickers hardness of a cross section (a plane parallel to the surface of the steel sheet) at a position of 1 / 4 of the thickness of the high-strength steel sheet is 85% or less of the hardness. The soft layer includes a decarburized layer in the surface layer of the high-strength steel sheet.

[0128] The surface layer soft layer refers to a soft layer included in the surface layer. The surface layer soft layer can be the entire surface layer or a part of the surface layer. The surface layer soft layer can be a region corresponding to a thickness of 200 μm or less in the thickness direction from the surface of the high-strength steel sheet.

[0129] For example, when a region in which the Vickers hardness of a cross section (a plane parallel to the surface of the steel sheet) at a position of 1 / 4 of the thickness of the high-strength steel sheet is 85% or less is formed at a prescribed depth in the thickness direction from the surface of the high-strength steel sheet, a region corresponding to a thickness from the surface to the prescribed depth in the thickness direction is the surface layer soft layer when the prescribed depth is 200 μm or less in the thickness direction, and a region corresponding to a thickness of 200 μm from the surface of the high-strength steel sheet to a depth of 200 μm in the thickness direction is the surface layer soft layer when the prescribed depth is greater than 200 μm in the thickness direction.

[0130] When the surface layer soft layer is present, the thickness of the surface layer soft layer is preferably 10 μm or more, more preferably 12 μm or more, and further preferably 15 μm or more. From the viewpoint of avoiding a decrease in TS, the thickness of the surface layer soft layer is preferably 150 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less.

[0131] Here, the thickness of the surface soft layer can be measured by the following method. After a plate thickness section (L section) parallel to the rolling direction of the base material steel sheet is smoothed by wet polishing, the Vickers hardness is measured at 1 μm intervals from the surface of the base material steel sheet to a position 100 μm in the plate thickness direction using a Vickers hardness tester with a load of 10 gf. Then, the measurement is performed at 20 μm intervals to the center of the plate thickness. The region in which the hardness is reduced to 85% or less of the hardness at the 1 / 4 position of the plate thickness is defined as the soft layer (surface soft layer), and the thickness in the plate thickness direction of this region is set as the thickness of the soft layer.

[0132] In the case where the surface soft layer is present, when the nano hardness of 300 or more points is measured in a region of 50 μm x 50 μm of the plate surface at a position 1 / 4 of the plate thickness direction depth from the surface of the high-strength steel sheet (a position 1 / 4 of the thickness of the surface soft layer in the depth direction from the surface of the high-strength steel sheet), the ratio of the nano hardness of 7.0 GPa or more is preferably 0.10 or less. When the ratio of the nano hardness of 7.0 GPa or more is 0.10 or less, it means that the ratio of hard structures (martensite, etc.), inclusions, and the like is small, and the generation of voids, the connection, and the progress of cracks of the hard structures (martensite, etc.), inclusions, and the like at the time of press forming and at the time of a collision can be further suppressed, and excellent bendability at the time of press forming and excellent bend fracture properties at the time of a collision can be easily obtained.

[0133] In the present application, in order to obtain excellent bendability at the time of press forming and excellent bend fracture properties at the time of a collision, the standard deviation σ of the nano hardness of the plate surface at a position 1 / 4 of the plate thickness direction depth of the surface soft layer from the surface of the high-strength steel sheet is 1.8 GPa or less, and further, the standard deviation σ of the nano hardness of the plate surface at a position 1 / 2 of the plate thickness direction depth of the surface soft layer from the surface of the high-strength steel sheet is preferably 2.2 GPa or less. When the standard deviation σ of the nano hardness of the plate surface at a position 1 / 4 of the plate thickness direction depth of the surface soft layer from the surface of the high-strength steel sheet is 1.8 GPa or less, and further, when the standard deviation σ of the nano hardness of the plate surface at a position 1 / 2 of the plate thickness direction depth of the surface soft layer from the surface of the high-strength steel sheet is 2.2 GPa or less, it means that the difference in the hardness of the microstructure is small, and the generation of voids, the connection, and the progress of cracks at the time of press forming and at the time of a collision can be further suppressed, and excellent bendability and excellent bend fracture properties at the time of a collision can be easily obtained.

[0134] Further, the more preferable range of the standard deviation σ of the nano hardness of the plate surface at a position 1 / 4 of the plate thickness direction depth of the surface soft layer from the surface of the high-strength steel sheet is 1.7 GPa or less. The more preferable range of the standard deviation σ of the nano hardness of the plate surface at a position 1 / 2 of the plate thickness direction depth of the surface soft layer from the surface of the high-strength steel sheet is 2.1 GPa or less.

[0135] Here, the nanohardness of the surface at the 1 / 4 position and the 1 / 2 position of the depth in the sheet thickness direction is the hardness determined by the following method.

[0136] First, when the plated layer is formed, it is the 1 / 4 position of the depth in the sheet thickness direction from the surface of the high-strength steel sheet to the surface layer soft layer after the plated layer is peeled off. The nanohardness is determined using a Berkovich-shaped diamond indenter under conditions in which the load is 500 μN, the measurement area is 50 μm x 50 μm, and the dot interval is 2 μm.

[0137] In addition, mechanical polishing is performed to the 1 / 2 position of the depth in the sheet thickness direction of the surface layer soft layer, polishing polishing is performed using diamond and alumina, and further colloidal silica polishing is performed. Then, the nanohardness is determined using a Berkovich-shaped diamond indenter under conditions in which the load is 500 μN, the measurement area is 50 μm x 50 μm, and the dot interval is 2 μm.

[0138] [1-6] Plated layer

[0139] Further, the high-strength steel sheet of the present application can have a plated layer on the surface.

[0140] 〈First plated layer〉

[0141] The high-strength steel sheet of the present application preferably has a first plated layer as a metal plated layer on the surface of one side or both sides of the base steel sheet. The first plated layer is formed directly on the surface of the base steel sheet, and is a metal plated layer containing one or two or more metals selected from the group consisting of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi in a total amount of more than 50 mass%, and is other than a hot-dip galvanized layer, an alloyed hot-dip galvanized layer, a zinc plated layer of an electro-galvanized layer, and a hot-dip aluminum plated layer. The first plated layer is preferably a metal plated layer, and hereinafter, the metal plated layer will be described by way of example.

[0142] By forming the metal plated layer on the surface of the steel sheet, the above-mentioned metal plated layer of the surface layer at the time of press forming and at the time of a vehicle body collision contributes to the suppression of the generation of a bending crack, thereby further improving the bending fracture resistance.

[0143] As the metal type of the metal plated layer, any one of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi can be used, but Fe is more preferable. Hereinafter, the Fe-based plated layer will be described by way of example.

[0144] The attachment amount of the Fe-based plated layer is more than 0 g / m 2, preferably 2.0 g / m 2 The upper limit of the attached amount of the Fe-based plated layer per one side is not particularly limited, and from the viewpoint of cost, the attached amount of the Fe-based plated layer per one side is preferably 60 g / m 2 The attached amount of the Fe-based plated layer is preferably 50 g / m 2 More preferably, it is 40 g / m 2 Further preferably, it is 30 g / m 2 Further preferably, it is 30 g / m

[0145] The attached amount of the Fe-based plated layer is measured as follows. A sample of 10 x 15 mm in size is taken from the Fe-based plated steel sheet and embedded in a resin as a cross-section embedded sample. Using a scanning electron microscope (SEM) at an acceleration voltage of 15 kV, the thickness of the Fe-based plated layer is observed at a magnification of 2000 to 10000 times for any three positions of the same cross-section, and the average of the thicknesses of the three fields is multiplied by the specific gravity of iron, whereby the attached amount of the Fe-based plated layer per one side is converted.

[0146] As the Fe-based plated layer, in addition to pure Fe, an alloy plated layer of Fe-B alloy, Fe-C alloy, Fe-P alloy, Fe-N alloy, Fe-O alloy, Fe-Ni alloy, Fe-Mn alloy, Fe-Mo alloy, Fe-W alloy, or the like can be used. The composition of the Fe-based plated layer is not particularly limited, and is preferably composed of: 10 mass% or less in total of one or two or more elements selected from B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V, and Co, and the remainder of Fe and unavoidable impurities. By making the amount of the elements other than Fe 10 mass% or less in total, a decrease in electrolytic efficiency can be prevented, and the Fe-based plated layer can be formed at low cost. In the case of the Fe-C alloy, the content of C is preferably 0.08 mass% or less.

[0147] 〈Second Plated Layer〉

[0148] In the high-strength steel sheet according to one embodiment of the present application, as the outermost layer on one side or both sides of the high-strength steel sheet, a second plated layer as a metal plated layer can also be provided. The second plated layer contains at least one of zinc and aluminum in a total amount of 50 mass% or more, and can be a hot-dip galvanized layer, an alloyed hot-dip galvanized layer, an electroplated zinc layer, a hot-dip aluminum layer, or the like.

[0149] The second plated layer can be formed directly on one side or both sides of the surface of the base steel sheet, or can be formed on the first plated layer.

[0150] Here, the hot-dip galvanized layer, the alloyed hot-dip galvanized layer, and the electroplated zinc layer refer to a plated layer in which Zn (zinc) is a main component (Zn content is 50.0 mass% or more).

[0151] In addition, the plated layer of the aluminum plated steel sheet refers to a plated layer in which Al (aluminum) is a main component (Al content is 50.0 mass% or more).

[0152] Here, the hot-dip galvanized layer is suitably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% to 1.0 mass% of Al. In addition, the hot-dip galvanized layer can arbitrarily contain, in a total amount of more than 0.0 mass% and 3.5 mass% or less, one or two or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM. Further, the Fe content of the hot-dip galvanized layer is more preferably less than 7.0 mass%. Note that the remaining portion other than the above elements is an unavoidable impurity.

[0153] In addition, the alloyed hot-dip galvanized layer is suitably composed of, for example, 20 mass% or less of Fe and 0.001 mass% to 1.0 mass% of Al. In addition, the alloyed hot-dip galvanized layer can arbitrarily contain, in a total amount of more than 0 mass% and 3.5 mass% or less, one or two or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM. The Fe content of the alloyed hot-dip galvanized layer is more preferably 7.0 mass% or more, and further preferably 8.0 mass% or more. The Fe content of the alloyed hot-dip galvanized layer is more preferably 15.0 mass% or less, and further preferably 12.0 mass% or less. Note that the remaining portion other than the above elements is an unavoidable impurity.

[0154] Further, the attachment amount of the above-described zinc plated layer per one surface is not particularly limited, and is preferably 20 g / m 2 ~ 80 g / m 2 .

[0155] The plating attachment amount of the above-described zinc plated layer is measured as follows. A treatment solution in which 0.6 g of a corrosion inhibitor for Fe (IBIT 700BK (registered trademark) manufactured by Asahi Chemical Industry Co., Ltd.) is added to 1 L of a 10 mass% hydrochloric acid aqueous solution is prepared. Next, a sample of a steel sheet having a zinc plated layer is immersed in the treatment solution, and the zinc plated layer is dissolved. Then, the mass reduction amount of the sample before and after the dissolution is measured, and the value is divided by the surface area of the base steel sheet (surface area of the plated layer portion), whereby the plating attachment amount (g / m 2 ) is calculated.

[0156] [2] Method for manufacturing high-strength steel sheet

[0157] Next, a manufacturing method of the high-strength steel sheet of the present application (hereinafter, also referred to as "manufacturing method") will be described. The manufacturing method of the present application is also a method of manufacturing the above-described high-strength steel sheet of the present application.

[0158] The manufacturing method of the high-strength steel sheet of the present application includes the following step: a step of casting molten steel having the above-described composition, and then, setting the average cooling rate in the temperature range of 500°C to 700°C to 3.0°C / hr or more, setting the average cooling rate in the temperature range of 400°C or higher and less than 500°C to 1.0°C / hr or more, and cooling to obtain a steel billet;

[0159] After heating the steel billet to a billet heating temperature T1 of 1150°C or higher, a hot-rolling step is performed in which the coiling temperature is set to 600°C or lower, and the residence time in the temperature range of 300°C to 400°C during cooling after coiling is set to 50,000 s or less, to obtain a hot-rolled sheet, and in the heating of the steel billet, the residence time in the temperature range of 1100°C to T1 is set to 20 minutes or more;

[0160] A step of performing pickling on the above-described hot-rolled sheet;

[0161] A step of performing cold-rolling on the hot-rolled sheet on which the above-described pickling has been performed, to manufacture a cold-rolled sheet;

[0162] A step of performing heating on the above-described cold-rolled sheet to a heating temperature T2 of Ac3 or higher, at an average heating rate of 10°C / s or more in the temperature range of 250°C to 700°C, to anneal the cold-rolled sheet, and setting the residence time in the temperature range of 750°C or higher and Ac3 or lower to 200 s or less;

[0163] A step of cooling the above-described cold-rolled sheet after annealing, at an average cooling rate of 1.0°C / s or more in the temperature range of 250°C to 400°C, to obtain a high-strength steel sheet.

[0164] [2-1] Steel Billet Manufacturing Step

[0165] The manufacturing method of the present application includes a step of melting a steel billet material having the composition of the high-strength steel sheet to manufacture a steel billet (billet). The melting method of the steel billet material is not particularly limited, and known melting methods such as a converter, an electric furnace, and the like are all suitable. For the steel billet, in order to prevent macro-segregation, it is preferable to be manufactured using a continuous casting method, but it can also be manufactured by an ingot casting method, a thin slab casting method, and the like.

[0166] In the manufacturing method of the present application, in cooling after melting the steel material, the average cooling rate in the temperature range of 500°C to 700°C is set to 3.0°C / hr or more, and the average cooling rate in the temperature range of 400°C or more and less than 500°C is set to 1.0°C / hr or more.

[0167] [average cooling rate in the temperature range of 500°C to 700°C: 3.0°C / hr or more]

[0168] In the manufacturing method of the present application, it is a key configuration that the average cooling rate in the temperature range of 500°C to 700°C is set to 3°C / hr or more, and by adopting this condition, it is possible to make the slab structure mainly as a low-temperature phase transformation phase. As a result, at the time of heating the slab in the next process, the local enrichment of Si is reduced, and it is possible to suppress the segregation of Si. In order to obtain such an effect, the average cooling rate in the temperature range of 500°C to 700°C is set to 3.0°C / hr or more, and preferably 5.0°C / hr or more. The upper limit of the average cooling rate in the temperature range of 500°C to 700°C is not particularly limited, and the thickness of the surface soft layer after annealing is controlled in an appropriate range, and from the aspect of obtaining a suitable TS, 100.0°C / hr or less is preferred.

[0169] Here, the temperature of the slab is set to the temperature of the surface of the slab.

[0170] [average cooling rate in the temperature range of 400°C or more and less than 500°C: 1°C / hr or more]

[0171] In the manufacturing method of the present application, it is a key configuration that the average cooling rate in the temperature range of 400°C or more and less than 500°C is set to 1°C / hr or more, and by adopting this condition, it is possible to make the slab structure mainly as a low-temperature phase transformation phase. As a result, at the time of heating the slab in the next process, the local enrichment of Si is reduced, and it is possible to suppress the segregation of Si. In order to obtain such an effect, the average cooling rate in the temperature range of 400°C or more and less than 500°C is set to 1.0°C / hr or more, and preferably 3.0°C / hr or more. The upper limit of the average cooling rate in the temperature range of 400°C or more and less than 500°C is not particularly limited, and the thickness of the surface soft layer after annealing is controlled in an appropriate range, and from the aspect of obtaining a suitable TS, 80.0°C / hr or less is preferred.

[0172] Here, the temperature of the slab is set to the temperature of the surface of the slab.

[0173] [2-2] Hot rolling process

[0174] The billet is heated to a slab heating temperature T1 of 1150°C or higher. At this time, the residence time in the temperature range of 1100°C to the slab heating temperature T1 is set to 20 minutes or more. The billet to be heated can be temporarily cooled to room temperature in the above-described process, or can be directly charged into a heating furnace in a warm piece state without cooling to room temperature, or the like.

[0175] [Slab heating temperature T1: 1150°C or higher]

[0176] By setting the slab heating temperature T1 to 1150°C or higher, local enrichment of Si is reduced, and segregation of Si can be suppressed. In order to obtain such an effect, the slab heating temperature T1 is set to 1150°C or higher, and preferably 1180°C or higher. The upper limit of the slab heating temperature T1 is not particularly limited, and the thickness of the surface soft layer after annealing is controlled within an appropriate range, and from the aspect of obtaining a suitable TS, it is preferably 1300°C or lower. The slab heating temperature T1 is preferably 1300°C or lower. Here, the slab heating temperature is the temperature of the surface of the slab.

[0177] [Residence time in the temperature range of 1100°C to the slab heating temperature T1: 20 minutes or more]

[0178] By setting the residence time in the temperature range of 1100°C to the slab heating temperature T1 to 20 minutes or more, local enrichment of Si is reduced, and segregation of Si can be suppressed. In order to obtain such an effect, the residence time in the temperature range of 1100°C to T1 is set to 20 minutes or more, and preferably 30 minutes or more. The upper limit of the residence time in the temperature range of 1100°C to the slab heating temperature T1 is not particularly limited, and the thickness of the surface soft layer after annealing is controlled within an appropriate range, and from the aspect of obtaining a suitable TS, it is preferably 300 minutes or less.

[0179] Here, the slab heating temperature is the temperature of the surface of the slab.

[0180] Next, the slab is subjected to hot rolling. The hot rolling can be composed of rough rolling and finish rolling.

[0181] The slab can be made into a thin slab, for example, by rough rolling. The conditions of the rough rolling are not particularly limited, and can be set to known conditions.

[0182] Next, the thin slab is subjected to finish rolling. The thin slab can also be heated using a bar heater or the like before finish rolling.

[0183] The finish rolling temperature is preferably the Ar3 transformation point or higher. If it is the Ar3 transformation point or higher, an increase in rolling load, an increase in reduction rate in the unrecrystallized state of austenite, and further, growth of abnormal structures elongated in the rolling direction can be suppressed, and a decrease in workability of the steel sheet obtained after annealing can be easily avoided.

[0184] The Ar3 transformation point is calculated by the following formula.

[0185] Ar3 (°C) = 868 - 396 x [%C] + 24.6 x [%Si] - 68.1 x [%Mn] - 36.1 x [%Ni] - 20.7 x [%Cu] - 24.8 x [%Cr]

[0186] In the formula, [%element symbol] represents the content (mass %) of the element in the composition.

[0187] The finishing can be performed continuously with the thin slabs being joined to each other. Alternatively, the thin slabs can be temporarily coiled before the finishing. Further, in order to reduce the rolling load, a part or all of the finishing can be performed as lubrication rolling. From the viewpoint of uniformization of the shape of the steel sheet and uniformization of the material, it is also effective to perform the lubrication rolling. The friction coefficient at the time of the lubrication rolling is preferably in the range of 0.10 to 0.25.

[0188] In the production method of the present application, it is particularly important to control the coiling temperature in the hot rolling step and the residence time in the temperature range of 300°C to 400°C in the cooling after the coiling.

[0189] [Coiling temperature: 600°C or less]

[0190] In the hot rolling step, after the finishing, the hot-rolled sheet is coiled, recovered, and then cooled. At this time, by setting the coiling temperature to 600°C or less, the hot-rolled structure can be made mainly as a low-temperature transformation phase. As a result, at the annealing in the final step, the local enrichment of Si is reduced, and the segregation of Si can be suppressed. In order to obtain such an effect, the coiling temperature is set to 600°C or less, and preferably 550°C or less. Since it is necessary to control the residence time in the temperature range of 300°C to 400°C in the cooling after the coiling, the coiling temperature is preferably 300°C or more.

[0191] [Residence time in the temperature range of 300°C to 400°C in the cooling after the coiling (hereinafter, residence time in the temperature range of 300°C to 400°C): 50,000 s or less]

[0192] After the hot-rolled sheet is coiled in a shape of a steel coil, it is left to stand in the temperature range of 300°C to 400°C for 50,000 s or less. Thereby, the hot-rolled structure can be made mainly as a low-temperature transformation phase. As a result, at the annealing in the final step, the local enrichment of Si is reduced, and the segregation of Si can be suppressed. In order to obtain such an effect, the residence time in the temperature range of 300°C to 400°C is set to 50,000 s or less, and preferably 30,000 s or less. The lower limit of the residence time in the temperature range of 300°C to 400°C is not particularly limited, and for example, even 2,000 s can give the desired characteristics.

[0193] The cooling conditions after the residence in the temperature range of 300°C to 400°C are not particularly limited, and known conditions can be employed. For example, the cooling rate is preferably 0.001°C / s to 1°C / s, and the cooling stop temperature is preferably 20°C to 200°C.

[0194] [2-3] Pickling Step

[0195] After the hot rolling step, the hot-rolled sheet is subjected to pickling. By the pickling, the oxides on the surface of the steel sheet can be removed, and good chemical conversion treatment properties and plating quality can be ensured. The pickling can be performed only once, or can be performed in multiple stages. The pickling conditions are not particularly limited, and known conditions can be employed.

[0196] [2-4] Heat Treatment Step (Optional)

[0197] After the pickling, the hot-rolled sheet can also be subjected to a heat treatment (hot-rolled sheet annealing). The heat treatment conditions are not particularly limited, and known conditions can be employed.

[0198] [2-5] Cold Rolling Step

[0199] Next, the hot-rolled sheet is subjected to cold rolling, and a cold-rolled sheet is produced. The cold rolling conditions are not particularly limited, and known conditions can be employed.

[0200] The cold rolling can be performed, for example, by a tandem multi-stand rolling mill or a reversing mill, or the like, for two or more rolling passes. The cumulative reduction rate of the cold rolling is preferably, for example, 20% to 75%. Note that the number of rolling passes, and the reduction rate of each pass are not particularly limited, and known conditions can be employed.

[0201] [2-6] First Plating Step (Optional)

[0202] In one embodiment of the present application, a first plating step can also be included, in which a first plated layer as a metal plated layer is formed on one side or both sides of the steel sheet after the hot rolling step (after the cold rolling step when cold rolling is performed) and before the annealing step. The first plating step is preferably a metal electroplating treatment step.

[0203] For example, a metal plating treatment (first plating treatment) such as metal electroplating treatment is performed on the surface of the cold-rolled sheet obtained as described above, and an annealing-preceding metal-plated steel sheet in which an annealing-preceding metal plated layer is formed on at least one side can be obtained. Note that the annealing-preceding metal plated layer referred to here can be the first plated layer described above. The annealing-preceding metal-plated steel sheet is preferably an annealing-preceding metal-electroplated steel sheet having an annealing-preceding metal electroplated layer.

[0204] The metal plating treatment method is not particularly limited, and as a metal plating layer formed on the base material steel sheet as described above, a metal plated layer is preferred, and thus it is preferred to perform metal plating treatment. For example, a sulfuric acid bath, a hydrochloric acid bath, or a mixture of both, or the like can be used in the Fe-based plating bath. In addition, the attached amount of the metal plated layer before annealing can be adjusted by the current application time, or the like. Note that the Fe-plated steel sheet before annealing refers to a state in which the metal plated layer has not been subjected to an annealing process, but does not exclude the case in which the hot-rolled sheet before the Fe plating treatment, the pickled sheet after the hot rolling, or the cold-rolled sheet is preliminarily annealed.

[0205] As the metal type of the metal plated layer, any one of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, Bi can be used, but Fe is more preferred, and thus the production method of the Fe-based plating is described below.

[0206] The Fe ion content in the Fe-based plating bath before the start of the current application is preferably 0.5 mol / L or more in terms of Fe 2+ If the Fe ion content in the Fe-based plating bath is 0.5 mol / L or more in terms of Fe 2+ In order to obtain a sufficient Fe attached amount, the Fe ion content in the Fe-based plating bath before the start of the current application is preferably 2.0 mol / L or less.

[0207] In addition, in the Fe-based plating bath, at least one element selected from B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V, and Co can be contained in addition to the Fe ion. The total content of these elements in the Fe-based plating bath is preferably such that the total content of these elements in the Fe-based plated layer before annealing is 10 mass% or less. Note that the metal elements can be contained as metal ions, and the non-metal elements can be contained as a part of boric acid, phosphoric acid, nitric acid, organic acid, or the like. In addition, conductivity aids such as sodium sulfate, potassium sulfate, chelating agents, and pH buffers can also be contained in the iron sulfate plating solution.

[0208] The other conditions of the Fe-based plating bath are not particularly limited. From the viewpoint of thermostatic retention, the temperature of the Fe-based plating solution is preferably 30°C or higher, and in addition, is preferably 85°C or lower. The pH of the Fe-based plating bath is also not particularly limited, and from the viewpoint of preventing a decrease in current efficiency due to the generation of hydrogen, it is preferably 1.0 or higher, and in addition, from the viewpoint of the conductivity of the Fe-based plating bath, it is preferably 3.0 or lower. With respect to the current density, from the viewpoint of productivity, it is preferably 10 A / dm 2 In addition, from the viewpoint of easily controlling the attached amount of the Fe-based plated layer, it is preferably 150 A / dm2 From the viewpoint of productivity, the sheet passing speed is preferably 5 mpm or more, and from the viewpoint of stably controlling the deposition amount, the sheet passing speed is preferably 150 mpm or less.

[0209] As the treatment before the Fe-based plating treatment, degreasing treatment and water washing for cleaning the surface of the cold-rolled steel sheet can be performed, and further, pickling treatment and water washing for activating the surface of the cold-rolled steel sheet can be performed. After these pretreatments, the Fe-based plating treatment is performed. The method of the degreasing treatment and the water washing is not particularly limited, and a general method can be used.

[0210] In the pickling treatment, various acids such as sulfuric acid, hydrochloric acid, nitric acid, and a mixture thereof can be used. Among them, sulfuric acid, hydrochloric acid, and a mixture thereof are preferred. The concentration of the acid is not particularly limited, and from the viewpoint of the ability to remove the oxide film and to prevent surface roughening (surface defects) and the like due to over-pickling, it is preferably 1 to 20 mass%.

[0211] In addition, a defoaming agent, a pickling accelerator, a pickling inhibitor, and the like can be contained in the pickling treatment solution.

[0212] [2-7] Annealing Step

[0213] The cold-rolled steel sheet obtained as described above or the cold-rolled steel sheet after the first plating step is subjected to annealing. The cold-rolled steel sheet can be a cold-rolled steel sheet after a metal plating treatment, but the treatment can not be performed. At the time of annealing, it is important to satisfy the following conditions.

[0214] [average heating rate in the temperature range of 250°C to 700°C: 10°C / s or more]

[0215] By increasing the average heating rate in the temperature range of 250°C to 700°C (hereinafter also referred to as "heating temperature range"), the austenite generated during heating is refined, and the local enrichment of Si is reduced, and as a result, segregation of Si can be suppressed. Therefore, the average heating rate in the temperature range of 250°C to 700°C is set to 10°C / s or more, preferably 12°C / s or more, and more preferably 14°C / s or more. The upper limit of the average heating rate in the temperature range of 250°C to 700°C is not particularly limited, and from the viewpoint of production technology constraints, it is preferably 50°C / s or less, and more preferably 40°C / s or less.

[0216] [residence time in the temperature range of 750°C or more and less than the Ac3 point: 200 s or less]

[0217] As a very important configuration in the present application, by shortening the residence time in the temperature region of 750°C or higher and less than the Ac3 point, the austenite generated in the heating is refined, and the local enrichment of Si is reduced, as a result of which the segregation of Si can be suppressed. From the viewpoint of obtaining such effects, the residence time in the temperature region of 750°C or higher and less than the Ac3 point is set to 200 s or less, preferably 150 s or less, and more preferably 120 s or less. The lower limit of the residence time in the temperature region of 750°C or higher and less than the Ac3 point is not particularly limited, and is preferably 10 s or more from the viewpoint of making the area ratio of the martensite an appropriate area ratio to make the TS more appropriate.

[0218] [Heating temperature T2: Ac3 point or higher]

[0219] When the heating temperature (annealing temperature) is Ac3 point or higher at T2, annealing treatment becomes a ferrite and austenite two-phase region, and thus a large amount of ferrite is contained after annealing, and it is difficult to achieve the desired TS and bendability. In addition, since the ferrite present before heating does not disappear at the heating temperature, the local enrichment of Si increases, and it is difficult to suppress the segregation of Si. Therefore, the heating temperature T2 is set to Ac3 point or higher, preferably (Ac3 point + 10°C) or higher, and more preferably (Ac3 point + 15°C) or higher. The upper limit of the heating temperature T2 is not particularly limited, and if the heating temperature T2 is increased, the thickness of the surface soft layer after annealing increases, and the TS can be reduced, and thus it is preferably 950°C or lower, and more preferably 920°C or lower.

[0220] The holding time at the heating temperature (annealing temperature) T2 is not particularly limited, and is preferably 10 s to 600 s.

[0221] Here, the heating temperature is measured based on the temperature of the surface of the steel sheet.

[0222] [Oxygen concentration in the atmosphere in the temperature region of 250°C to 700°C: 2 volume ppm to 30 volume ppm (appropriate condition)]

[0223] When the cold-rolled sheet is annealed, by increasing the oxygen concentration in the temperature region of 250°C to 700°C, decarburization is performed by oxygen in the air, and a surface soft layer can be formed, and as a result, more appropriate bendability can be achieved. From the viewpoint of obtaining such effects, the oxygen concentration in the temperature region of 250°C to 700°C is preferably 2 volume ppm or more, more preferably 4 volume ppm or more, and further preferably 5 volume ppm or more. On the other hand, as the oxygen concentration in the temperature region of 250°C to 700°C increases, the thickness of the surface soft layer after annealing increases, and the TS can be reduced, and thus the oxygen concentration in the temperature region of 250°C to 700°C is preferably 30 volume ppm or less, more preferably 28 volume ppm or less, and further preferably 25 volume ppm or less.

[0224] Here, the temperature in the temperature range of 250°C to 700°C is based on the steel sheet surface temperature. That is, when the steel sheet surface temperature is in the above-mentioned temperature range of 250°C to 700°C, the oxygen concentration is adjusted to the above-mentioned range.

[0225] [Dew point of the atmosphere at the heating temperature T2: -35°C or higher (preferable condition)]

[0226] By raising the dew point of the atmosphere at the heating temperature T2, decarburization is performed by moisture in the air at the time of annealing of the cold-rolled sheet, and a surface layer soft layer can be formed, as a result of which more preferable bendability can be achieved. From the viewpoint of obtaining such an effect, the dew point at the heating temperature T2 is preferably -35°C or higher, more preferably -30°C or higher, and further preferably -25°C or higher. The upper limit of the dew point at the heating temperature T2 is not particularly limited, and from the viewpoint of controlling the thickness of the surface layer soft layer after annealing to a suitable range and obtaining more suitable TS, the dew point at the heating temperature T2 is preferably 15°C or lower, and more preferably 5°C or lower.

[0227] Here, the heating temperature T2 is based on the steel sheet surface temperature. That is, when the steel sheet surface temperature is the above-mentioned heating temperature T2, the dew point is adjusted to the above-mentioned range.

[0228] In the cooling after heating, the average cooling rate at a temperature lower than the heating temperature T2 and greater than 400°C is not particularly limited, and is preferably 5°C / s or higher and 30°C / s or lower. In addition, the high-strength steel sheet can be temporarily cooled at a temperature lower than the heating temperature T2 and greater than 400°C, and the steel sheet temperature can be raised again.

[0229] [2-8] Cooling step

[0230] [Average cooling rate in the temperature range of 250°C to 400°C: 1.0°C / s or higher]

[0231] When the average cooling rate in the temperature range of 250°C to 400°C is less than 1.0°C / s, a large amount of bainite ferrite is contained after annealing, and it is difficult to achieve the desired TS, YR, and bendability. Therefore, the average cooling rate in the temperature range of 250°C to 400°C is set to 1.0°C / s or higher, preferably 2.0°C / s or higher, and more preferably 3.0°C / s or higher. The upper limit of the average cooling rate in the temperature range of 250°C to 400°C is not particularly limited, and from the viewpoint of constraints in production technology, it is preferably 1000°C / s or lower, preferably 100.0°C / s or lower, and more preferably 80.0°C / s or lower.

[0232] Here, the average cooling rate is measured based on the temperature of the steel sheet surface.

[0233] The cooling method in the temperature range of 250°C to 400°C is not particularly limited, and for example, gas jet cooling, water mist cooling, water cooling, air cooling, or the like can be applied.

[0234] [Insulation temperature T3 in cooling step: 100°C or higher and 450°C or lower (optimum condition)]

[0235] In the cooling step, by performing insulation to the high-strength steel sheet, TS, YR, and bendability can be made to be in a more suitable range. In order to obtain such an effect, the insulation temperature T3 in the cooling step is preferably 100°C or higher, more preferably 150°C or higher, and further preferably 200°C or higher. On the other hand, as the insulation temperature in the cooling step increases, the area ratio of bainite ferrite increases and TS decreases, and thus the insulation temperature T3 in the cooling step is preferably 450°C or lower, more preferably 400°C or lower, and further preferably 350°C or lower.

[0236] Here, the temperature in the cooling step is based on the steel sheet surface temperature.

[0237] [Insulation time in cooling step: 5 s or more (optimum condition)]

[0238] By performing insulation in the cooling step, TS, YR, and bendability can be made to be in a more suitable range. In order to obtain such an effect, the insulation time at the insulation temperature T3 in the cooling step is preferably 5 s or more, more preferably 10 s or more, and further preferably 15 s or more. On the other hand, the upper limit of the insulation time at the insulation temperature T3 in the cooling step is not particularly limited, and from the viewpoint of obtaining a suitable TS, the insulation time at the insulation temperature T3 in the cooling step is preferably 500 s or less, and more preferably 250 s or less.

[0239] When the insulation temperature T3 is in the temperature range of 250°C to 400°C, the average cooling speed in the above-described temperature range of 250°C to 400°C is set to the average cooling speed at the time of cooling other than the insulation process at the insulation temperature T3. This average cooling speed can be calculated from the average cooling speed from 250°C to T3 and the average cooling speed from T3 to 400°C.

[0240] [Cooling stop temperature T4: 250°C or lower (optimum condition)]

[0241] If the cooling stop temperature T4 exceeds 250°C, a large amount of bainite ferrite is contained after annealing, and it is difficult to achieve the desired TS, YR, and bendability. Therefore, the cooling stop temperature is set to 250°C or lower, and preferably 200°C or lower. On the other hand, the lower limit of the cooling stop temperature T4 is not particularly limited, and from the viewpoint of productivity, it is preferably room temperature or higher.

[0242] Here, the cooling stop temperature is measured based on the temperature of the surface of the steel sheet.

[0243] The average cooling rate from 2500C to the cooling stop temperature T4 is not particularly limited, and in order to further improve the TS, the average cooling rate in the temperature range below 2500C and below T4 is preferably 1°C / s or more, and more preferably 2°C / s or more. On the other hand, from the viewpoint of production technology, the average cooling rate in the temperature range below 2500C and below T4 is preferably 1000°C / s or less, and more preferably 150°C / s or less.

[0244] The cold-rolled sheet can be cooled to room temperature from the cooling stop temperature T4. The average cooling rate from the cooling stop temperature T4 to room temperature is not particularly limited, and cooling to room temperature can be performed by any method. As the cooling method, gas jet cooling, water mist cooling, water cooling, and air cooling, etc. can be applied.

[0245] After the annealed cold-rolled sheet is cooled to the cooling stop temperature T4, rolling can be performed at an elongation of 0.05% to 2.00%. By performing rolling at an elongation of 0.05% or more after cooling to T4, the YR can be controlled to a desired range. The elongation is more preferably 0.10% or more. In addition, by performing rolling at an elongation of 2.00% or less after cooling to T4, the volume fraction of retained austenite can be in a more suitable range, and the degree of damage to the sheared end surface in a bending test and in a corrosion environment can be in a more suitable range. The elongation is more preferably 1.00% or less.

[0246] The rolling after cooling to the cooling stop temperature T4 can be performed on a device continuous with the above-described continuous annealing device (on-line), or can be performed on a device discontinuous with the above-described continuous annealing device (off-line). In addition, the target elongation can be achieved by one rolling, or multiple rollings can be performed to achieve an elongation of 0.05% to 2.00% in total. Note that the rolling described herein generally refers to quenching rolling, but as long as an elongation equivalent to quenching rolling can be applied, a method in which processing is performed by repeatedly bending using a tension leveller, a roll, or the like can also be used.

[0247] [2-9] Reheating Step

[0248] [Reheating Temperature: (Cooling Stop Temperature T4 + 50°C) or more and 450°C or less (Suitable Condition)]

[0249] By subjecting the high-strength steel sheet to reheating after cooling to the cooling stop temperature T4, or after further performing rolling after cooling to T4, it is possible to bring TS, YR, and bendability within a more suitable range. From the viewpoint of obtaining such effects, the reheating temperature is preferably (cooling stop temperature T4 + 50°C) or higher, more preferably (cooling stop temperature T4 + 100°C) or higher, and further preferably (cooling stop temperature T4 + 150°C) or higher

[0250] On the other hand, as the reheating temperature is increased, the martensite is tempered, and TS decreases, and thus the reheating temperature is preferably 450°C or lower, more preferably 400°C or lower, and further preferably 380°C or lower.

[0251] Here, the temperature of the above-mentioned heating temperature range is based on the steel sheet surface temperature. That is, when the steel sheet surface temperature is within the above-mentioned heating temperature range, the oxygen concentration is adjusted to the above-mentioned range.

[0252] [Soaking time at reheating temperature: 5 s or more (suitable conditions)]

[0253] By performing soaking at the reheating temperature, it is possible to bring TS, YR, and bendability within a more suitable range. In order to obtain such effects, the soaking time at the reheating temperature is preferably 5 s or more, more preferably 10 s or more, and further preferably 15 s or more. On the other hand, the upper limit of the soaking time at the reheating temperature is not particularly limited, and in order to bring TS within a more suitable range, the soaking time at the reheating temperature is preferably 500 s or less, and further preferably 250 s or less.

[0254] Note that the cooling rate from the above-mentioned reheating temperature to room temperature is not particularly limited, and cooling to room temperature can be performed by any method. As the cooling method, gas jet cooling, water mist cooling, water cooling, and air cooling, etc. can be applied.

[0255] [2-10] Second plating treatment step (arbitrary)

[0256] A high-strength steel sheet manufactured as described above can be subjected to plating treatment to produce a plated steel sheet. For example, as the plating treatment, hot-dip galvanizing treatment, and treatment for alloying after hot-dip galvanizing can be exemplified. In addition, annealing and galvanizing can also be performed continuously on one production line. Furthermore, a plated layer can also be formed by electroplating of Zn-Ni alloy or the like, or hot-dip galvanizing of Zn-Al-Mg alloy can also be performed. Note that the above-mentioned description has been made centering on the case of galvanizing, but the kind of plated metal such as Zn, Al, etc. is not particularly limited.

[0257] In the case of the hot-dip galvanizing treatment, the steel sheet is preferably immersed in a galvanizing bath at 440°C to 500°C, and then the plated adhesion amount is adjusted by gas wiping or the like. As the hot-dip galvanizing bath, there is no particular limitation as long as the composition of the zinc plating layer is as described above, and for example, a plating bath having a composition in which the Al content is 0.10 mass% to 0.23 mass% and the remainder is composed of Zn and unavoidable impurities is preferably used.

[0258] In the case of the alloyed galvanizing treatment, after the hot-dip galvanizing treatment is performed in accordance with the above-mentioned procedure, the steel sheet having the hot-dip galvanizing layer (hot-dip galvanized steel sheet) is heated to an alloying temperature of 450°C or higher and 600°C or lower, and the alloying treatment is performed. When the alloying temperature is less than 450°C, the Zn-Fe alloying speed becomes slow, and sometimes the alloying is difficult. On the other hand, if the alloying temperature exceeds 600°C, the untransformed austenite phase is transformed into pearlite, and it is difficult to make the TS 590 MPa or higher. It should be noted that the alloying temperature is more preferably 510°C or higher. In addition, the alloying temperature is more preferably 570°C or lower.

[0259] In addition, the plated adhesion amount of the steel sheet having the hot-dip galvanizing layer (hot-dip galvanized steel sheet) (GI) and the steel sheet having the alloyed hot-dip galvanizing layer (alloyed hot-dip galvanized steel sheet) (GA) is preferably 20 to 80 g / m2per one side. 2 It should be noted that the plated adhesion amount can be adjusted by gas wiping or the like.

[0260] In addition, in the case of the hot-dip aluminum plating treatment which is cited as a specific example of the plating treatment with another metal, the cold-rolled sheet obtained by annealing the above-mentioned cold-rolled sheet is immersed in an aluminum plating bath at 660°C to 730°C, the hot-dip aluminum plating treatment is performed, and then the plated adhesion amount is adjusted by gas wiping or the like.

[0261] Further, in the case of the electro-galvanizing treatment, there is no particular limitation, and the film thickness is preferably made in the range of 2 μm to 15 μm.

[0262] [2-11] Skin pass rolling (optional)

[0263] The skin pass rolling can also be performed after the plating treatment.

[0264] The reduction rate in the skin pass rolling is preferably 0.05% or higher from the viewpoint of increasing the yield strength. The upper limit of the reduction rate is not particularly limited, and is preferably 1.50% from the viewpoint of productivity.

[0265] The skin pass rolling can be performed on-line or off-line.

[0266] The skin pass rolling to the target reduction rate can be performed at one time or can be divided into several times.

[0267] From the viewpoint of productivity, the series of processes such as the annealing and plating treatment described above are preferably performed on a CGL (Continuous Galvanizing Line).

[0268] In the case where the high-strength plated steel sheet is taken as a transaction object, it is generally taken as a transaction object after being cooled to room temperature.

[0269] The manufacturing conditions other than the above-described conditions can be performed according to a conventional method.

[0270] [3] Parts and automobile members

[0271] Next, the parts of the present application are described.

[0272] The parts of the present application are parts in which at least a part is made of the high-strength steel sheet of the present application described above. The parts of the present application are obtained, for example, by forming the high-strength steel sheet of the present application described above into a target shape by press working or the like. The parts of the present application are suitably used for automobile members (for example, for automobile skeletal structural members, for automobile reinforcing members, or the like).

[0273] The present application also relates to automobile members composed of the parts of the present application.

[0274] The high-strength steel sheet of the present application has a high YR and a high bendability, and is a high-strength steel sheet having a TS of 1180 MPa or higher in which the corrosion resistance of the sheared end surface is high. Therefore, the parts of the present application can contribute to the weight reduction of a vehicle body, and thus can be applied to all parts for automobile members (for example, for automobile skeletal structural members or for automobile reinforcing members).

[0275] Examples

[0276] [Tests No. 1 to 47]

[0277] A steel having the composition shown in Table 1 and the balance consisting of Fe and inevitable impurities was melted in a converter, and a slab was produced by a continuous casting method. The obtained slab was heated, and after hot rolling, pickling treatment was performed, and then cold rolling was performed. Subsequently, annealing treatment was performed, and a high-strength cold-rolled sheet (CR) was obtained. Furthermore, plating treatment was performed on a part of the thin steel sheet, and a hot-dip galvanized steel sheet (GI), an alloyed hot-dip galvanized steel sheet (GA), and an electrogalvanized steel sheet (EG) were obtained. The manufacturing conditions of the steel sheets are described in Table 2.

[0278] As for the hot-dip galvanizing bath, a zinc bath containing Al: 0.14 to 0.19 mass% was used in the case of GI, and a zinc bath containing Al: 0.14 mass% was used in the case of GA, and the bath temperature was 470°C. As for the plating attached amount, it was 45 to 72 g / m 2 (both sides plating) in the case of GI, and 45 g / m2 (both sides plating) left and right. In addition, in the case of GA, the Fe concentration in the plated layer was set to 9 to 12 mass%. In the case of EG in which the plated layer was a Zn-Ni plated layer, the Ni content in the plated layer was 9 to 25 mass%.

[0279] For the steel sheet thus obtained, the steel structure, the standard deviation of the Si concentration at the 1 / 2 position of the sheet thickness / average Si concentration, and the thickness of the surface soft layer were measured.

[0280] [Steel structure]

[0281] The area ratio of the martensite and ferrite at the 1 / 4 position of the sheet thickness and the volume ratio of the residual austenite were calculated in the above-described manner. The remaining structure was observed in the following manner. After a test piece was cut out in a manner such that the sheet thickness section (L section) parallel to the rolling direction of the steel sheet was the observation surface, mirror polishing was performed on the observation surface using a diamond polishing paste, and then, fine polishing was performed using colloidal silica, and further, etching was performed using 3% by volume nitric acid ethanol to make the structure appear. Using an SEM at an accelerating voltage of 15 kV, 3 fields of view were observed at a magnification of 5000 times in a field of view range of 17 μm x 23 μm at the 1 / 4 position of the sheet thickness of the steel sheet as the observation position. From the obtained structure image, carbides were recognized as the remaining structure.

[0282] [Standard deviation of Si concentration at 1 / 2 position of sheet thickness / average Si concentration]

[0283] The standard deviation of the Si concentration at the 1 / 2 position of the sheet thickness / average Si concentration was calculated in the above-described manner.

[0284] [Thickness of surface soft layer]

[0285] After a sheet thickness section (L section) parallel to the rolling direction of the base material steel sheet was smoothed by wet polishing, the Vickers hardness tester was used to measure the hardness at 1 μm intervals from the surface of the base material steel sheet in the sheet thickness direction up to a position 100 μm in the sheet thickness direction. Then, the measurement was performed at 20 μm intervals up to the center of the sheet thickness. The region in which the hardness was reduced to 85% or less of the hardness at the 1 / 4 position of the sheet thickness was defined as the soft layer (surface soft layer), and the thickness in the sheet thickness direction of this region was set as the thickness of the soft layer.

[0286] For the steel sheet thus obtained, the tensile properties, the bendability, and the damage degree of the sheared end surface in a corrosive environment were evaluated in the following test methods. The results are shown in Table 3.

[0287] [Tensile test]

[0288] The tensile test was performed according to JIS Z2241. From the obtained steel sheet, JIS No. 5 test pieces were collected in a direction at right angles to the rolling direction of the steel sheet, and a tensile test was performed at a crosshead speed of 1.67 x 10 -1 mm / s, and YS and TS were measured. Note that, in the present application, TS of 1180 MPa or more was judged to be acceptable. In addition, excellent dimensional accuracy of the member means that the index of the dimensional accuracy of the member, i.e., the yield ratio (YR), was 65% or more, and this case was judged to be good. Note that YR was calculated according to the calculation method described in the above formula (2).

[0289] [Bending Test]

[0290] The bending test was performed according to JIS Z2248. From the obtained steel sheet, a strip-shaped test piece having a width of 30 mm and a length of 100 mm was collected in a direction parallel to the rolling direction of the steel sheet as the axial direction of the bending test. Then, under conditions of a press-in load of 100 kN and a press-in holding time of 5 seconds, a 90° V-bending test was performed. Note that, in the present disclosure, the bendability was evaluated using the acceptance rate of the bending test, and the maximum R (for example, when the plate thickness is 1.2 mm, the bending radius is 6.0 mm) obtained by dividing the bending radius (R) by the plate thickness (t) was 5 or less, the bending test was performed on 5 samples, and then, whether or not a crack was generated at the ridge line portion of the bending apex was evaluated, and the case where no crack was generated in all 5 samples was evaluated as "excellent" in bendability. In addition, the case where a crack of 200 μm or less was generated in one or more of the 5 samples was judged to be "good" in bendability. Furthermore, the case where a crack of 200 μm or more was generated in one or more of the 5 samples was judged to be "poor" in bendability. Here, whether or not a crack was generated was evaluated by measuring the ridge line portion of the bending apex at a magnification of 40 times using a digital microscope (RH-2000: manufactured by HiROX Corporation).

[0291] [Damage Degree of Sheared End Surface in Corrosion Environment]

[0292] A strip-shaped test piece having a width (direction at right angles to the rolling direction): 75 mm and a length (rolling direction): 18 mm was sheared from the obtained steel sheet in a direction at right angles to the rolling direction of the steel sheet as the shearing separation surface, using a toggle press. Note that the shearing conditions of the toggle press were set to a shearing angle of 0.5 degrees and a gap of 10%. Next, the side that was peeled off during shearing of the toggle press was ground by 2 mm, and a strip-shaped test piece having a width of 75 mm and a length of 16 mm was prepared.

[0293] Next, a load stress equivalent to YS was applied in a four-point bending test, then, immersion in hydrochloric acid with constant management of pH at pH 3 was performed for 120 hours, then, the strip test piece was taken out and washed with running water. Next, the strip test piece was cut off in parallel with the rolling direction from the central position of the width of the strip test piece as the observation position. Next, after mirror polishing the cut surface of the test piece, the test piece was observed at a magnification of 1000 times using SEM on the sheared surface of the test piece, and the case where the length of the crack on the sheared surface of the test piece, i.e., the length of the crack after the hydrochloric acid immersion, was 300 μm or less was judged to be good.

[0294]

[0295]

[0296]

[0297] Table 3

[0298]

[0299] Underlined portion: indicates out of range

[0300] M: martensite, α: ferrite and / or bainitic ferrite, residual γ: residual austenite, θ: cementite and / or metastable carbide;

[0301] As shown in Table 3, in the inventive examples, TS was 1180 MPa or more, YR, bendability, and the degree of damage of the sheared end surface in a corrosion environment were excellent. On the other hand, in the comparative examples, any one or more of TS, YR, bendability, and the degree of damage of the sheared end surface in a corrosion environment was inferior.

[0302] [Tests Nos. 48 to 80]

[0303] A steel having the composition shown in Table 1 and the remainder consisting of Fe and inevitable impurities was melted in a converter, and a slab was produced by a continuous casting method. The obtained slab was heated, and after hot rolling, pickling treatment was performed, and then cold rolling was performed.

[0304] A metal plating treatment step was performed on a part of the cold-rolled steel sheet. In the presence / absence of metal plating treatment (plating layer type) column of Table 4, when it was (Fe), it was an example in which Fe-based plating treatment was performed, and when it was (Ni), it was an example in which Ni-based plating treatment was performed. As for the composition of the metal plating layer, Fe: 95 to 100 mass% was contained in the case of Fe-based plating, and Ni: 95 to 100 mass% was contained in the case of Ni-based plating, and each of the remaining portions was an inevitable impurity.

[0305] Next, the cold-rolled steel sheet was subjected to plating treatment (GI, GA) of the kinds shown in Table 4 to obtain a plated steel sheet having a hot-dip galvanized layer on both sides. The conditions of GI, GA were the same as described above.

[0306] Next, a holding treatment or a cooling and then heating treatment was performed under the conditions shown in Table 4. The conditions not specifically specified were performed according to the conventional method.

[0307] The composition of the base steel sheet of the obtained steel sheet was substantially the same as the composition at the billet stage, and the steel was within the range of the composition described in the above embodiment.

[0308] For the steel sheet thus obtained, the steel structure, the standard deviation of the Si concentration at the 1 / 2 position of the sheet thickness / average Si concentration, and the thickness of the surface soft layer were measured. In addition, the metal plating layer adhesion amount was measured, and the nano hardness of the surface soft layer was measured. The results are shown in Table 5.

[0309] [Nano hardness of surface soft layer]

[0310] For the high-strength plated steel sheet, after the plating layer (hot-dip galvanized layer or alloyed zinc plated layer, metal plated layer as the case can be) was peeled, mechanical polishing was performed to a position of 1 / 4 of the depth in the sheet thickness direction of the surface soft layer from the surface of the base steel sheet, and polishing with diamond and alumina and colloidal silica polishing were performed. Using a tribo-950 of Hysitron, Inc., nano hardness was measured for a total of 512 points under the conditions of a Berkovich-shaped diamond indenter, load: 500 μN, measurement area: 50 μm x 50 μm, and dot interval: 2 μm.

[0311] Next, mechanical polishing was performed to a position of 1 / 2 of the depth in the sheet thickness direction of the surface soft layer, and polishing with diamond and alumina and colloidal silica polishing were performed. Using a tribo-950 of Hysitron, Inc., nano hardness was measured for a total of 512 points under the conditions of a Berkovich-shaped diamond indenter, load: 500 μN, measurement area: 50 μm x 50 μm, and dot interval: 2 μm.

[0312] The obtained steel sheet was evaluated for the tensile properties, bendability, and damage degree of the sheared end surface in a corrosive environment in the same manner as described above. The results are shown in Table 5.

[0313] Further, the obtained steel sheets were subjected to U-bending + close bending test, V-bending + orthogonal VDA bending test, and axial crush test. In view of the influence of the sheet thickness, in these tests, steel sheets having a sheet thickness of 1.2 mm were used. Steel sheets having a sheet thickness greater than 1.2 mm were single-sidedly ground to have a sheet thickness of 1.2 mm. Since the grinding process can affect the bendability of the steel sheet surface, in the bending test of the U-bending + close bending, the ground surface was set to the inside (valley side) of the bend, in the V-bending + orthogonal VDA bending test, the ground surface was set to the outside (hill side) of the bend in the V-bending test, and the ground surface was set to the inside (valley side) of the bend in the subsequent VDA bending test. On the other hand, in the U-bending + close bending test, the V-bending + orthogonal VDA bending test, and the axial crush test of the zinc-plated steel sheet having a sheet thickness less than 1.2 mm, since the influence of the sheet thickness is small, the tests were performed without the grinding process.

[0314] [U-bending + close bending test]

[0315] The U-bending + close bending test was performed as follows.

[0316] From the obtained steel sheets, a test piece of 60 mm x 30 mm was collected by shearing and end-face grinding. Here, the 60 mm side was parallel to the width (C) direction. The test piece was prepared by U-bending processing (primary bending processing) in the width (C) direction with the rolling (L) direction as the axis, with a curvature radius / sheet thickness of 4.2. Figure 1 (a), the punch B1 was pressed into the steel sheet placed on the roll Al to obtain a test piece T1. Subsequently, as shown in Figure 1 (b), the test piece T1 placed on the lower die A2 was subjected to close bending (secondary bending processing) by extrusion using the upper die B2. In Figure 1 (a), D1 indicates the width (C) direction, and D2 indicates the rolling (L) direction. Note that a spacer S described later was interposed between the test pieces.

[0317] The conditions of the U-bending in the U-bending + close bending test were as follows.

[0318] Test method: roll support, punch press-in

[0319] Punch tip R: 5.0 mm

[0320] Gap between roll and punch: sheet thickness + 0.1 mm

[0321] Stroke speed: 10 mm / min

[0322] Bending direction: rolling right angle (C) direction

[0323] The conditions of the close bending in the U-bending + close bending test were as follows.

[0324] Gasket thickness: varied at 0.5 mm intervals

[0325] Test method: die support, punch press-in

[0326] Molding load: 10 tons

[0327] Test speed: 10 mm / min

[0328] Holding time: 5 s

[0329] Bending direction: rolling right angle (C) direction

[0330] The above U-bending + close bending test was performed three times, and when no cracks were generated in the three times, it was regarded as the limit gasket thickness (ST). In addition, using a stereo microscope manufactured by Leica, cracks having a length of 200 μm or more were determined as cracks at a magnification of 25 times. Note that ST is an index for evaluating the fracture resistance at the time of impact (fracture resistance of the longitudinal wall portion in the axial crushing test). The results are shown in Table 5.

[0331] The criteria for the pass of the limit gasket thickness (ST) are as follows.

[0332] 1180 MPa ≤ TS < 1320 MPa, 5.5 mm ≥ ST

[0333] 1320 MPa ≤ TS, 6.0 mm ≥ ST

[0334] The criteria for the fail of the limit gasket thickness (ST) are as follows.

[0335] 1180 MPa ≤ TS < 1320 MPa, 5.5 mm < ST

[0336] 1320 MPa ≤ TS, 6.0 mm < ST

[0337] [V-bending + orthogonal VDA bending test]

[0338] The V-bending + orthogonal VDA bending test was performed as follows.

[0339] From the obtained steel sheet, a test piece of 60 mm x 65 mm was collected by shearing and end face grinding. Here, the 60 mm side was parallel to the rolling (L) direction. A 90° bending process (one bending process) was performed in the rolling (L) direction with the width (C) direction as the axis with a curvature radius / plate thickness of 4.2, and a test piece was prepared. In the 90° bending process (one bending process), as shown in (a), punch B3 was pressed into the steel sheet placed on die A3 having a V groove, and a test piece T1 was obtained. Next, as shown in (b), punch B4 was pressed into the test piece T1, and a test piece T2 was obtained. Figure 2 (a) shown, punch B3 was pressed into the steel sheet placed on die A3 having a V groove, and a test piece T1 was obtained. Next, as shown in (b), punch B4 was pressed into the test piece T1, and a test piece T2 was obtained. Figure 2(b) shown, relative to the test piece Tl placed on the support roll A4, the punch B4 is pressed in such a way that the bending direction becomes the rolling straight angle direction, and orthogonal bending (second bending process) is performed. In Figure 2 (a) and Figure 2 (b), Dl indicates the width (C) direction, and D2 indicates the rolling (L) direction.

[0340] The conditions of the V-bending in the V-bending + orthogonal VDA-bending test are as follows.

[0341] Test method: die support, punch press-in

[0342] Molding load: 10 tons

[0343] Test speed: 30 mm / min

[0344] Hold time: 5 s

[0345] Bending direction: rolling (L) direction

[0346] The conditions of the VDA-bending in the V-bending + orthogonal VDA-bending test are as follows.

[0347] Test method: roll support, punch press-in

[0348] Roll diameter: φ 30 mm

[0349] Punch tip R: 0.4 mm

[0350] Roll distance: (plate thickness x 2) + 0.5 mm

[0351] Stroke speed: 20 mm / min

[0352] Test piece size: 60 mm x 60 mm

[0353] Bending direction: rolling straight angle (C) direction

[0354] In the stroke-load curve obtained when the above-described VDA-bending is performed, the stroke at the time of maximum load is found. The average value of the stroke at the time of maximum load when the above-described V-bending + orthogonal VDA-bending test is performed three times is taken as SF max (mm). It should be noted that SF max is an index for evaluating the fracture resistance at the time of collision (fracture resistance of the bending ridge portion in the axial crush test). The results are shown in Table 5.

[0355] SF max The pass criteria for SF

[0356] 24.5 mm ≤ SF max

[0357] 1470 MPa < TS, 23.5 mm < SF max

[0358] SF max The criteria for disqualification are as follows.

[0359] 1180 MPa < TS < 1470 MPa, 24.5 mm > SF max

[0360] 1470 MPa < TS, 23.5 mm > SF max

[0361] [Axial crush test]

[0362] The axial crush test was performed as follows.

[0363] From the obtained steel sheet, a test piece of 150 mm x 100 mm was collected by shearing. Here, the 150 mm side was parallel to the rolling (L) direction. Using a die having a punch shoulder radius of 5.0 mm and a die shoulder radius of 5.0 mm, a hat-shaped member 10 as shown in Figure 3 (a) and Figure 3 (b) was produced by forming processing to a depth of 40 mm (bending processing). In addition, a steel sheet to be used as a base material of the hat-shaped member was additionally cut to a size of 80 mm x 100 mm. Subsequently, the cut steel sheet 20 was spot-welded to the hat-shaped member 10 to produce a test member 30 as shown in Figure 3 (a) and Figure 3 (b). Figure 3 (a) is a front view of the test member 30 produced by spot-welding the hat-shaped member 10 to the steel sheet 20. Figure 3 (b) is a perspective view of the test member 30. As shown in Figure 3 (b), the position of the spot-welding portion 40 was such that the end of the steel sheet was spaced apart from the welding portion by 10 mm and the welding portions were spaced apart by 20 mm. Subsequently, as shown in Figure 3 (c), the test member 30 was joined to a base plate 50 by TIG welding to produce a sample for the axial crush test. Subsequently, an impactor 60 was made to collide with the produced sample for the axial crush test at a collision speed of 10 mm / min to crush the sample for the axial crush test by 70 mm. As shown in Figure 3 (c), the direction of crushing was a direction parallel to the long side direction of the test member 30. The results are shown in Table 5.

[0364] The criteria for evaluation of the presence or absence of axial crush fracture (appearance cracks) are as follows.

[0365] A (pass): No appearance cracks were observed in the sample after the axial crush test.

[0366] B (Pass): 1 or less of the appearance cracks are observed in the sample after the axial crush test C (Fail): 2 or more of the appearance cracks are observed in the sample after the axial crush test

[0367]

[0368]

[0369] As shown in Table 5, in the inventive examples, TS is 1180 MPa or more, YR, bendability, and the degree of damage of the sheared end surface in the corrosion environment are excellent. On the other hand, in the comparative examples, any one or more of TS, YR, bendability, and the degree of damage of the sheared end surface in the corrosion environment is poor. In addition, in Table 5, in the range where the dew point is -30°C to -20°C, the thickness of the soft layer of the surface layer is 14 μm or less, and the determination of the fracture (appearance crack) in the axial crush test is "B", in the case where the thickness of the soft layer of the surface layer is 14 μm or less but has a metallic plating layer, the determination of the fracture (appearance crack) in the axial crush test is "A".

[0370] The embodiment of the present application has been described above, but the present application is not limited to the description that constitutes a part of the disclosure of the present application of the present embodiment. That is, other embodiments, examples, and application technologies performed by those skilled in the art and the like according to the present embodiment are all included in the scope of the present application. For example, in the series of heat treatments in the above manufacturing method, the equipment and the like for performing the heat treatment on the steel sheet are not particularly limited as long as the thermal process conditions are satisfied.

[0371] Industrial applicability

[0372] According to the present application, a high-strength steel sheet having a TS of 1180 MPa or more, high YR, and high bendability, and a reduced degree of damage of the sheared end surface in the corrosion environment can be obtained.

[0373] In particular, the high-strength steel sheet of the present application can be applied to skeletal structural members and the like of automobiles of various sizes and shapes while obtaining high member strength because the degree of damage of the sheared end surface in the corrosion environment is reduced. Thus, improvement in fuel economy due to the lightening of the vehicle body can be achieved, and the industrial applicability is extremely great.

[0374] Explanation of symbols

[0375] 10 Hat-shaped member

[0376] 20 Galvanized steel sheet

[0377] 30 Test member

[0378] 40 Spot-welded portion

[0379] 50 Floor panel

[0380] 60 punch

[0381] A1 die

[0382] A2 backup roll

[0383] A3 die

[0384] A4 backup roll

[0385] B1 punch

[0386] B2 punch

[0387] B3 punch

[0388] B4 punch

[0389] D1 width (C) direction

[0390] D2 rolling (L) direction

[0391] S shim

[0392] T1 test piece

[0393] T2 test piece

Claims

1. A high-strength steel sheet having a composition consisting of, in mass%, C: 0.030 to 0.500%, Si: 0.01 to 2.50%, Mn: 0.10 to 5.00%, P: 0.100% or less, S: 0.0200% or less, Al: 1.000% or less, N: 0.0100% or less, and O: 0.0100% or less, with the balance consisting of Fe and unavoidable impurities, and a steel structure in which, at a position of 1 / 4 of a sheet thickness, the area fraction of martensite is 40% or more, the area fraction of ferrite is 70% or less, and the volume fraction of residual austenite is 20.0% or less, and in which, at a position of 1 / 2 of the sheet thickness, the ratio of the standard deviation of the Si concentration to the average value of the Si concentration is 1.00 or less. The composition further contains, in mass%, at least one element selected from the group consisting of Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 0.010% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, and Bi: 0.200% or less. The high-strength steel sheet has a surface soft layer which is a region having a Vickers hardness of 85% or less with respect to the Vickers hardness at a position of 1 / 4 of a sheet thickness of the high-strength steel sheet, and which is a region within 200 μm in a sheet thickness direction from a surface of the high-strength steel sheet, When the nano hardness of 300 or more points is measured in a region of 50 μm x 50 μm of each surface at a position of 1 / 4 of a sheet thickness depth from the surface of the high-strength steel sheet to the surface soft layer and at a position of 1 / 2 of the sheet thickness depth, 2. The high-strength steel sheet according to claim 1, wherein The proportion of the number of points at which the nano hardness of the surface at the position of 1 / 4 of the sheet thickness depth from the surface of the high-strength steel sheet to the surface soft layer is 7.0 GPa or more, with respect to the total number of points measured, is 0.10 or less, 3. The high-strength steel sheet according to claim 1 or 2, wherein, The standard deviation σ of the nano hardness of the surface at the position of 1 / 4 of the sheet thickness depth from the surface of the high-strength steel sheet to the surface soft layer is 1.8 GPa or less, The standard deviation σ of the nano hardness of the surface at the position of 1 / 2 of the sheet thickness depth from the surface of the high-strength steel sheet to the surface soft layer is 2.2 GPa or less. ​ ​ ​ 4. The high-strength steel sheet according to any one of claims 1 to 3, wherein, A metal plating layer containing one or two or more kinds selected from the group consisting of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi in a total amount of 50% by mass or more is provided on one or both surfaces of the high-strength steel sheet.

5. The high-strength steel sheet according to any one of claims 1 to 4, wherein, A metal plating layer containing at least one of zinc and aluminum in a total amount of 50% by mass or more is provided as the outermost layer on one or both surfaces of the high-strength steel sheet.

6. A method for manufacturing a high-strength steel sheet, comprising the following steps: a step of casting molten steel having the composition according to claim 1 or 2, and then cooling the molten steel at an average cooling rate of 3.0°C / hr or more in a temperature range of 500°C to 700°C, and at an average cooling rate of 1.0°C / hr or more in a temperature range of 400°C or higher and less than 500°C, to obtain a steel slab; a step of heating the steel slab to a slab heating temperature Tl of 1150°C or higher, and then hot-rolling the steel slab at a coiling temperature of 600°C or lower and a residence time of 50000 seconds or less in a temperature range of 300°C to 400°C during cooling after the coiling, to obtain a hot-rolled sheet, wherein in the heating of the steel slab, a residence time in a temperature range of 1100°C to Tl is set to 20 minutes or more; a step of pickling the hot-rolled sheet; a step of cold-rolling the hot-rolled sheet subjected to the pickling, to obtain a cold-rolled sheet; a step of annealing the cold-rolled sheet by heating the cold-rolled sheet to a heating temperature T2 of Ac3 or higher at an average heating rate of 10°C / s or more in a temperature range of 250°C to 700°C, wherein a residence time in a temperature range of 750°C or higher and less than Ac3 is set to 200 seconds or less, and the temperature defined by the following formula (1) is set as the Ac3 point in °C: and a step of cooling the annealed cold-rolled sheet at an average cooling rate of 1.0°C / s or more in a temperature range of 250°C to 400°C, to obtain a high-strength steel sheet. Ac3 point (°C) = 910 - 203 [%C] 1 / 2 + 44.7 [%Si] - 30 [%Mn] + 700 [%P] + 400 [%Al] + 400 [%Ti] + 104 [%V] + 13.1 [%W] - 11 [%Cr] + 31.5 [%Mo] - 15.2 [%Ni] - 20 [%Cu]... (1) In the formula, [%X] represents the content of the component element X in the steel in % by mass, and is set to 0 when the component element X is not contained.

7. The method of producing a high-strength steel sheet according to claim 6, wherein In the annealing step of the cold-rolled sheet, the oxygen concentration of the atmosphere in a temperature range of 250°C to 700°C is 2 to 30 ppm by volume, and the dew point of the atmosphere at the heating temperature T2 is -35°C or higher.

8. The method of producing a high-strength steel sheet according to claim 6 or 7, wherein In the cooling step of the annealed cold-rolled sheet, a holding step is provided at a temperature T3 of 100°C or higher and 450°C or lower for 5 seconds or more.

9. The method of producing a high-strength steel sheet according to any one of claims 6 to 8, wherein In the cooling step of the annealed cold-rolled sheet, the cooling is stopped at a cooling stop temperature T4 of 250°C or lower, and then reheating is performed to a temperature of (T4 + 50°C) or higher and 450°C or lower, and the temperature is held for 5 seconds or more.

10. The method of producing a high-strength steel sheet according to any one of claims 6 to 9, wherein The process includes the following steps: before annealing the cold-rolled sheet, plating a metal containing more than 50 mass% in total of one or more selected from Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi on one or both sides of the cold-rolled sheet.

11. The method of producing a high-strength steel sheet according to any one of claims 6 to 10, wherein The process includes the following steps: after cooling the annealed cold-rolled sheet, plating a metal containing more than 50 mass% in total of at least one of zinc and aluminum.

12. A member comprising at least a portion of the high-strength steel sheet according to any one of claims 1 to 5.

13. An automobile member comprising the member according to claim 12.

Citation Information

Patent Citations

  • Hot-dip galvanized steel sheet and method for producing the same

    JP2012219342A